Fabric care unit dose article having capsules
By using capsules of water-soluble fiber non-woven matrix and inorganic material shells in the water-soluble single agent article, the problems of water-soluble single agent article in the prior art in terms of environmental sustainability and performance benefits are solved, and better fabric care and environmental protection performance are achieved.
Patent Information
- Application Number
- JP2024558410
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-12
- Filing Date
- 2023-04-11
- Publication Date
- 2025-04-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing water-soluble single agent articles have problems with environmental sustainability, using a large number of petrochemical systems, and have poor performance and benefits.
Using a single dose of water-soluble fiber non-woven matrix and a granule therapeutic component containing an inorganic material shell, the adhesion and retention effect on fabrics is improved through the combination of water-soluble polymer fibers and core-shell-type capsules.
Achieve better fabric care performance, while reducing dependence on petrochemical systems and reducing environmental impact.
Smart Images

Figure 2025512924000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a water-soluble unit dose article comprising a water-soluble fibrous nonwoven substrate and a particulate treatment composition, the composition comprising a capsule, the capsule having a shell comprising an inorganic material. The disclosure also relates to an associated method of treating fabrics. [Background technology]
[0002] Water-soluble unit dose articles are convenient and efficient to use, and are therefore favored by consumers.Such water-soluble unit dose articles often contain laundry treatment compositions, which may be encapsulated by a water-soluble substrate, such as a water-soluble film.When the article comes into contact with water, the substrate dissolves and releases the laundry treatment composition into the water, thereby producing an aqueous treatment solution.
[0003] Such laundry treatment compositions may comprise core-shell capsules, where the benefit agent (such as perfume) in the core is surrounded by the shell.The shell is typically made from petrochemical-based technology, such as melamine formaldehyde or polyacrylate-based technology.In recent years, for environmental sustainability reasons, formulators have been searching for ways to reduce the content of petrochemical-based in their formulations.In addition, when such capsules are formulated into water-soluble unit dose products, it has been found that the performance benefits delivered are suboptimal. Summary of the Invention [Problem to be solved by the invention]
[0004] Thus, there is a need for improved fabric care products in the form of water soluble unit dose articles that provide improved performance benefits and are characterized by a lower environmental impact due to reduced petrochemical-derived content. [Means for solving the problem]
[0005] The present disclosure relates to water-soluble unit dose articles and related fabric treatment methods.
[0006] For example, the present disclosure relates to a water soluble unit dose article comprising a water soluble fibrous nonwoven substrate and a particulate treatment composition, wherein the substrate comprises a plurality of fibers, the fibers comprise a water soluble polymer, the particulate treatment composition comprises a capsule, the capsule comprises a core and a shell surrounding the core, the core comprises a benefit agent, and the shell comprises an inorganic material.
[0007] The present disclosure also relates to a method of treating fabrics comprising combining water with a water soluble unit dose article according to the present disclosure to form a treatment solution, and contacting the fabrics with the treatment solution, preferably in the drum of an automatic washing machine. [Brief description of the drawings]
[0008] The drawings herein are illustrative in nature and are not intended to be limiting. [Figure 1] 1 shows a water soluble unit dose article according to the present disclosure. [Diagram 2] 2 shows a cross-section of the article of FIG. 1. [Diagram 3] FIG. 1 shows a schematic diagram of an exemplary nonwoven substrate in which capsules are mixed with the fibers of the water soluble fibrous nonwoven substrate. [Figure 4] FIG. 1 is a schematic diagram of a method for making a capsule having a first shell component prepared with a hydrophobic core. [Diagram 5] FIG. 1 is a schematic diagram of a capsule having a first shell component and a second shell component. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present disclosure relates to a water-soluble unit dose article comprising a fabric treatment composition and related methods. The article comprises a water-soluble fibrous nonwoven substrate, for example in the form of a sheet or pouch, and the substrate comprises a water-soluble polymer. The fabric treatment composition comprises a core-shell capsule with a shell comprising an inorganic material. It has been found that such a unit dose article can provide a surprisingly good performance benefit to target fabrics. For example, when the capsule contains perfume in the core, a surprisingly good freshness benefit is observed.
[0010] Without wishing to be bound by theory, it is believed that there is a synergy between the water-soluble polymer of the substrate according to the present disclosure and the capsules having inorganic shell materials, which results in improved adhesion and retention of the capsules on the fabric during washing, compared to when these perfume capsules having shell materials according to the present invention are incorporated into a non-water-soluble substrate-encapsulated fabric treatment composition, thereby improving the overall performance of the fabric.
[0011] This is even more surprising considering that when comparing petrochemically derived encapsulated fragrance technologies, they have been found to negatively interact with similar water soluble polymers, resulting in compromised performance when compared to formulating comparables in the absence of such water soluble polymers.
[0012] The capsules, compositions, substrates, articles, and related methods are described in further detail below.
[0013] As used herein, the articles "a" and "an" when used in a claim are understood to mean one or more of what is claimed or described. As used herein, the terms "include", "includes" and "including" are meant to be open-ended. The compositions of the present disclosure may comprise, consist essentially of, or consist of the components of the present disclosure.
[0014] The terms "substantially free of" or "substantially free from" may be used herein. This means that the indicated material is in minimal amounts and has not been intentionally added to the composition to form part of the composition, or preferably is not present at analytically detectable concentrations. It means that it includes compositions in which the indicated material is present only as an impurity in one of the other intentionally included materials. The indicated material may be present, if at all, at a concentration of less than 1% by weight of the composition, or less than 0.1% by weight, or less than 0.01% by weight, or even 0% by weight.
[0015] As used herein, the phrase "treatment composition" includes compositions and formulations designed to treat fabrics. Such compositions include, but are not limited to, laundry cleaning compositions and detergents, fabric softening compositions, fabric enhancing compositions, fabric freshening compositions, laundry pre-wash, laundry pre-treatment, laundry additives, dry cleaning agents or compositions, laundry rinse additives, cleaning additives, post-rinse fabric treatments, etc. Such compositions can be used as laundry pre-treatments, laundry post-treatments, or can be added during the rinse or wash cycle of a laundry operation.
[0016] Unless otherwise noted, all component or composition concentrations are in terms of the active portion of that component or composition and are exclusive of impurities, e.g., residual solvents or by-products, that may be present in commercial sources of such component or composition.
[0017] All temperatures herein are in degrees Celsius (° C.) unless otherwise indicated. All measurements herein are made at 20° C. and atmospheric pressure unless otherwise stated.
[0018] In all embodiments of the present disclosure, all percentages are by weight of the total composition unless otherwise specified. All ratios are by weight unless otherwise specified.
[0019] It should be understood that every maximum numerical limitation given throughout this specification includes every lower numerical limitation, as if such lower numerical limitations were expressly written herein. Every minimum numerical limitation given throughout this specification includes every higher numerical limitation, as if such higher numerical limitations were expressly written herein. Every numerical range given throughout this specification includes every narrower numerical range that falls within such broader numerical range, as if such narrower numerical ranges were all expressly written herein.
[0020] Unit dose items The present disclosure relates to a water-soluble unit dose article. The article is useful for treating fabrics. The water-soluble unit dose article includes a water-soluble fibrous nonwoven substrate and a particulate treatment composition, the particulate treatment composition including core-shell capsules.
[0021] The water soluble fibrous nonwoven substrate, which may be in the form of a sheet, may be molded to form at least one sealed interior compartment, with the treatment composition contained within the sealed interior compartment.
[0022] The unit dose article may include a first fibrous nonwoven sheet and a second water-soluble fibrous nonwoven sheet sealed together to define an internal compartment. The water-soluble unit dose article is configured to prevent leakage of the granular detergent composition from the compartment during storage. However, when the water-soluble unit dose article is added to water, the water-soluble nonwoven fibrous sheet dissolves and releases the contents of the internal compartment into the wash liquor.
[0023] Compartment is understood to mean the closed internal space in the unit dose article that holds the particulate treatment composition. During manufacture, the first water-soluble fiber nonwoven sheet may be molded to include an open compartment into which the detergent composition is added. Then, the second water-soluble fiber nonwoven sheet can be placed on the first sheet in an orientation that closes the opening of the compartment. The first sheet and the second sheet are then sealed together along the seal area.
[0024] Alternatively, a single water-soluble fibrous nonwoven fabric may be formed into an open container. The granular laundry detergent composition can then be filled into the open container, and the open container can then be sealed closed.
[0025] A unit dose article may contain one or more compartments, or even at least two compartments, or even at least three compartments. The compartments may be located in a side-by-side orientation, i.e., one adjacent to the other. Alternatively, one compartment may be completely enclosed within another compartment.
[0026] When the unit dose article comprises at least two compartments, one of the compartments may be smaller than the other compartment.
[0027] Each compartment may contain the same composition or a different composition.
[0028] The unit dose article may include two or more plies of nonwoven substrate, preferably three or more plies. The plies may be connected by any suitable method, such as by sealing at one or more edges of the article. In such cases, there may be little or no space between the plies. In other words, in such cases, the article may not include a compartment. The article may include two or more plies stacked on top of each other. The article may be formed by folding a sheet of nonwoven substrate on itself to form two or more plies. Individual articles may be cut from the stacked and / or folded substrate layers.
[0029] FIG. 1 discloses a water-soluble unit dose article (1) according to the present disclosure. The water-soluble unit dose article (1) shown has a generally rectangular shape. However, it may have any suitable shape, including a square, a triangle, a circle, an oval, a hexagon, or a mixture thereof. The water-soluble unit dose article (1) comprises a water-soluble fibrous nonwoven substrate (2) in the form of a sheet.
[0030] As can be seen in FIG. 2, which is a cross-sectional view of the water-soluble unit dose article (1) of FIG. 1, the water-soluble fibrous nonwoven substrate (2) is molded to create at least one internal compartment (3) that contains the fabric treatment composition (4) in particulate form.
[0031] FIG. 3 shows a schematic cross-sectional view of an exemplary water-soluble nonwoven substrate (2). The nonwoven substrate (2) comprises fibers (5) intertwined with each other to form a fibrous structure. Delivery capsules (6) according to the present disclosure may be mixed with the fibers (3) to form a coform structure (7). Additional particles (8) may also be mixed with the fibers (3). The additional particles (8) may comprise a processing aid. The additional particles (8) may be particles of an acid and / or a salt thereof, preferably citric acid and / or a salt thereof. The additional particles (8) may be detergent particles comprising detergent adjunct ingredients such as surfactants as described below.
[0032] In the water soluble unit dose articles of the present disclosure, the treatment composition or portions thereof may be encapsulated within one or more compartments, may be mixed with a plurality of fibers, or may be present as a combination thereof.
[0033] The unit dose articles of the present disclosure may take the form described in US Pat. No. 10,526,570, which is incorporated by reference.
[0034] Water-soluble nonwoven fabric base material The water-soluble unit dose article comprises a water-soluble fibrous nonwoven substrate. The water-soluble fibrous nonwoven sheet comprises a plurality of fibers. Preferably, the fibers are intertwined fibers in the form of a fibrous structure. As used herein, "fiber" and "fiber" may be used interchangeably.
[0035] The water soluble fibrous nonwoven substrate may be in the form of a sheet or web and may be cut to a suitable size, folded onto itself, and / or laminated with another substrate, including another nonwoven sheet.
[0036] The water-soluble fibrous nonwoven sheet may be homogeneous or layered, and if layered, may comprise at least two, and / or at least three, and / or at least four, and / or at least five layers.
[0037] The water-soluble fiber nonwoven sheet may have a basis weight of 20 gsm to 60 gsm, preferably 20 gsm to 55 gsm, more preferably 25 gsm to 50 gsm, and most preferably 25 gsm to 45 gsm. The basis weight of the water-soluble fiber nonwoven sheet may be 55 gsm to 5000 gsm, preferably 250 gsm to 3000 gsm, more preferably 500 gsm to 2500 gsm, and most preferably 1000 gsm to 2000 gsm. A person skilled in the art will recognize known methods for measuring basis weight. When the basis weight is measured on a water-soluble fiber nonwoven sheet containing particles and / or active substance-containing particles, the basis weight ranges referred to herein are meant to include the basis weight of the combined fiber and particle nonwoven sheet. A top-loading analytical balance with a sensitivity limit of ±0.001 g is used to measure the basis weight of the water-soluble fiber nonwoven sheet with 12 usable units stacked. A wind shield is used to protect the balance from air currents and other disturbances. All samples are prepared using a precision cut die measuring 8.9 cm±0.009 cm by 8.9 cm±0.009 cm.
[0038] Using a precision cutting die, cut the specimens into squares. Stack the cut squares together to a thickness of 12 specimens. Measure the mass of the stacked specimens and record the result to the nearest 0.001 g.
[0039] The basis weight in g / m2 is as follows: 2 Calculate as follows. Basis weight = (mass of stacked samples) / [(area of one square in stacked samples) x (number of squares in stacked samples)]
[0040] "Fiber" as used herein means an elongated element having a length greater than its average diameter, preferably with a ratio of length to average diameter of at least about 10.
[0041] Preferably, each fiber may have a length of 5.08 cm or greater, 7.62 cm or greater, 10.16 cm or greater, 15.24 cm or greater, or a mixture thereof.
[0042] Alternatively, each fiber may have a length of less than 5.08 cm, less than 3.81 cm, less than 2.54 cm, or a mixture thereof.
[0043] Each fiber may have a width of less than 100 μm, less than 75 μm, less than 50 μm, less than 25 μm, less than 10 μm, less than 5 μm, less than 1 μm, or a mixture thereof. Those skilled in the art will recognize standard methods for measuring width. Preferred methods include scanning electron microscopy (SEM) or optical microscopy with image analysis software.
[0044] The water-soluble fiber nonwoven sheet may comprise a plurality of fibers that are identical or substantially identical in terms of composition. Alternatively, the water-soluble fiber nonwoven sheet may comprise two or more different fibers according to the present invention. Non-limiting examples of differences in fibers may include physical differences such as differences in diameter, length, texture, shape, stiffness, elasticity, etc., and chemical differences such as crosslinking concentration, solubility, melting point, Tg, active agent, etc.
[0045] Preferably, the fibers are present in an amount of 80% to 95% by weight, preferably 85% to 93% by weight, more preferably 87% to 90% by weight of the water-soluble fibrous nonwoven sheet.
[0046] The water-soluble fibrous nonwoven sheet may exhibit different regions, e.g., regions of different basis weight, density, and / or caliper. The water-soluble fibrous nonwoven sheet may include a texture on one or more of its surfaces. The surface of the water-soluble fibrous nonwoven sheet may include a pattern, such as a non-random repeating pattern. The outer surface of the substrate may include printing, e.g., indicia such as graphics or letters. The unit dose article may include an aversive agent, such as a bitter agent, preferably on at least the outer surface of the nonwoven substrate.
[0047] The water-soluble fiber nonwoven sheet may have a thickness of 0.01 mm to 100 mm, preferably 0.05 mm to 50 mm, more preferably 0.1 mm to 20 mm, even more preferably 0.1 mm to 10 mm, even more preferably 0.1 mm to 5 mm, even more preferably 0.1 mm to 2 mm, even more preferably 0.1 mm to 0.5 mm, and most preferably 0.1 mm to 0.3 mm. Those skilled in the art will be aware of standard methods for measuring thickness.
[0048] The fibers include a water-soluble polymer. Suitable water-soluble polymers include polyvinyl alcohol, polyvinylpyrrolidone, starch, carboxymethylcellulose, polyethylene oxide, derivatives thereof, combinations thereof, and other suitable polymers, especially hydroxyl-containing polymers and / or derivatives thereof, such as starch and / or starch derivatives, such as ethoxylated starch, acetylated starch, and / or acid-diluted starch, carboxymethylcellulose, hydroxypropylcellulose, hydroxyethylcellulose, and derivatives thereof, or combinations thereof. Preferably, the water-soluble polymer is polyvinyl alcohol. Preferably, the fibers include 50% to 98% by weight of the fiber, preferably 65% to 97% by weight, more preferably 80% to 96% by weight, and even more preferably 88% to 96% by weight of the fiber.
[0049] The polyvinyl alcohol polymer may have a weight average molecular weight of about 5 kDa to about 200 kDa, preferably about 10 kDa to about 150 kDa, more preferably about 20 kDa to about 120 kDa. The polyvinyl alcohol polymer may have a weight average molecular weight of about 50 kDa to about 150 kDa, preferably about 60 kDa to about 130 kDa, more preferably about 8 kDa to about 120 kDa, and such molecular weights are considered to be particularly useful when the substrate forms a pouch or compartment. The polyvinyl alcohol polymer may have a weight average molecular weight of about 5 kDa to about 70 kDa, preferably about 7 kDa to about 65 kDa, more preferably about 10 kDa to about 60 kDa, and even more preferably about 20 kDa to about 50 kDa, and such molecular weights are considered to be particularly useful when the substrate includes particles mixed with fibers. As used herein, "weight average molecular weight" refers to the weight average molecular weight determined using gel permeation chromatography according to the protocol found in Colloids and Surfaces A. Physico Chemical & Engineering Aspects, Vol. 162, 2000, pg. 107-121. Those skilled in the art will recognize other known techniques for determining weight average molecular weight (MW).
[0050] Preferably, the polyvinyl alcohol polymer is a polyvinyl alcohol homopolymer. Preferably, the polyvinyl alcohol homopolymer has an average percentage degree of hydrolysis of 75% to 100%, preferably 80% to 95%, most preferably 85% to 90%. Preferably, the polyvinyl alcohol homopolymer has an average viscosity of 1 to 30 mPas, preferably 5 to 25 mPas, most preferably 10 to 20 mPas, the viscosity being measured as a 4% aqueous solution in demineralized water at 20°C.
[0051] In addition to the water-soluble polymer, the fiber may also include one or more active agents. The nonwoven substrate, sheet, and / or article of the present invention may include one or more active agents. Both the fiber and the nonwoven substrate / sheet and / or article may include one or more active agents. For example, the active agent may be selected from the group consisting of: personal cleansing and / or conditioning agents, such as hair care agents (e.g., shampoos and / or hair dyes), hair conditioning agents, skin care agents, sunscreens, and skin conditioning agents; laundry care and / or conditioning agents, such as fabric care agents, fabric conditioning agents, fabric softeners, fabric wrinkle inhibitors, fabric care antistatic agents ... stain removers, soil release agents, dispersants, foam suppressors, foam boosters, defoamers, and fabric refreshing agents; liquid and / or powder dishwashing agents (for hand dishwashing and / or automatic dishwashing applications), hard surface care agents, and / or conditioning agents and / or abrasives; other cleaning and / or conditioning agents, such as antimicrobial agents, antibacterial agents, antifungal agents, fabric tinting agents, fragrances, bleaching agents (e.g., oxygen bleach, hydrogen peroxide, percarbonate bleach, perborate bleach, , chlorine bleach), bleach activators, chelating agents, builders, lotions, brighteners, air care agents, carpet care agents, dye transfer inhibitors, clay stain removers, anti-redeposition agents, polymeric stain release agents, polymeric dispersants, alkoxylated polyamine polymers, alkoxylated polycarboxylate polymers, amphiphilic graft copolymers, dissolution aids, buffer systems, water softeners, water hardeners, pH adjusters, enzymes, flocculants, foaming agents, preservatives, cosmetic agents, make-up removers, foaming agents, deposition aids, coacervate formers, clays, thickeners, latex, silica, drying agents, odor control agents, antiperspirants, cooling agents, warming agents, absorbent gelling agents, anti-inflammatory agents, dyes, pigments, acids and bases; liquid treatment actives; agricultural actives; industrial actives; ingestible actives such as pharmaceutical agents, tooth whitening agents, tooth care agents, mouthwashes, periodontal and gingival care agents, edible agents, edible agents, vitamins, minerals; water treatment agents such as water clarifiers and / or water disinfectants, and mixtures thereof.
[0052] The fibers preferably comprise from 0.1% to 15% by weight of the fiber of a gel breaking agent, the gel breaking agent being selected from a polyol, a sugar alcohol, an amine, an amide, a carbohydrate, a polyvalent cation, or mixtures thereof, preferably a polyol, a sugar alcohol, or mixtures thereof. Preferably, the fibers comprise from 1% to 12%, preferably from 2% to 10%, by weight of the fiber of a gel breaking agent.
[0053] Without wishing to be bound by theory, polyols are synthetic materials, while sugar alcohols are naturally occurring materials. Sugar alcohols can include ribose, xylose, fructose, or mixtures thereof.
[0054] Preferably, the gel breaker is selected from glycerol, polyethylene glycol, 1,2-propanediol, dipropylene glycol, 2-methyl-1,3-propanediol, triethylene glycol, polyethylene glycol, sorbitol, cyclohexanedimethanol, hexylene glycol, dipropylene glycol n-butyl ether, 2-methyl-2,4-pentanediol, polypropylene glycol, urea, formamide, ethanolamine, carbohydrates, dianhydrohexitol, magnesium chloride, and mixtures thereof, preferably selected from polyethylene glycol, glycerol, sorbitol, dipropylene glycol, and mixtures thereof.
[0055] Preferably, the fibers comprise 0.1% to 15%, preferably 1% to 12%, more preferably 2% to 10% by weight of the fiber of a gel breaker selected from the group consisting of glycerol, polyethylene glycol, 1,2-propanediol, dipropylene glycol, 2-methyl-1,3-propanediol, triethylene glycol, polyethylene glycol, sorbitol, cyclohexanedimethanol, hexylene glycol, dipropylene glycol n-butyl ether, 2-methyl-2,4-pentanediol, polypropylene glycol, urea, formamide, ethanolamine, carbohydrates, dianhydrohexitol, magnesium chloride, and mixtures thereof. Preferably, the fibers comprise 0.1% to 15%, preferably 1% to 12%, more preferably 2% to 10% by weight of the fiber of a gel breaker selected from the group consisting of polyethylene glycol, glycerol, sorbitol, dipropylene glycol, and mixtures thereof.
[0056] Preferably, the fibers comprise from 0.1% to 15%, preferably from 1% to 12%, more preferably from 2% to 10% by weight of the fiber of a gel breaker selected from glycerol, polyethylene glycol, 1,2-propanediol, dipropylene glycol, 2-methyl-1,3-propanediol, triethylene glycol, polyethylene glycol, sorbitol, cyclohexanedimethanol, hexylene glycol, dipropylene glycol n-butyl ether, 2-methyl-2,4-pentanediol, polypropylene glycol, urea, formamide, ethanolamine, carbohydrates, dianhydrohexitol, magnesium chloride, and mixtures thereof. Preferably, the fibers comprise from 0.1% to 15%, preferably from 1% to 12%, more preferably from 2% to 10% by weight of the fiber of a gel breaker, and the fibers comprise from 0.1% to 15%, preferably from 1% to 12%, more preferably from 2% to 10% by weight of the fiber of a gel breaker selected from polyethylene glycol, glycerol, sorbitol, dipropylene glycol, and mixtures thereof.
[0057] Preferably, the weight average molecular weight of the polyethylene glycol is 100-800, preferably 200-750, more preferably 400-700, and even more preferably 500-650. As used herein, "weight average molecular weight" refers to the weight average molecular weight determined using gel permeation chromatography according to the protocol found in Colloids and Surfaces A. Physico Chemical & Engineering Aspects, Vol. 162, 2000, pg. 107-121. Those skilled in the art will recognize other known techniques for determining weight average molecular weight (MW).
[0058] The fibrous nonwoven substrate may include particles. The particles may be, in part or in whole, particles of a particulate treatment composition. The particles may include capsules of the present disclosure. Without being bound by theory, the fibrous nonwoven substrate includes gaps or spaces between the fibers. When present, the particles in the substrate are preferably present in the gaps / spaces between the fibers. The particles may be present at a concentration of 0.25% to 10%, preferably 0.5% to 5%, more preferably 1% to 3% by weight of the water-soluble fibrous nonwoven substrate. The particles may include capsules according to the present disclosure, acids, zeolites, inorganic salts, surfactant granules or mixtures thereof. Preferably, the inorganic salts include sodium carbonate, sodium chloride, sodium sulfate or mixtures thereof. Preferably, the particles in the nonwoven substrate have an average particle size distribution of 1 micron to 150 microns, preferably 5 microns to 125 microns, more preferably 10 microns to 100 microns. The particles may be water-soluble or water-insoluble. The nonwoven sheet and / or article may include water-soluble particles and / or water-insoluble particles. As referred to herein, the particles may include active agent-containing particles. The particles may be present in the nonwoven sheet and / or article in a weight ratio of particles, e.g., active agent-containing particles, to fibers of 1:100 or more and / or 1:50 or more and / or 1:10 or more and / or 1:3 or more and / or 1:2 or more and / or 1:1 or more and / or about 10:1 to about 1:100 and / or about 7:1 to about 1:50 and / or about 7:1 to about 1:10 and / or about 7:1 to about 1:3 and / or about 6:1 to 1:2 and / or about 5:1 to about 1:1 and / or about 4:1 to about 1:1 and / or about 3:1 to about 1.5:1. Non-limiting examples of suitable particles and particle concentrations are described in U.S. Pat. No. 8,980,816, which is incorporated by reference.
[0059] Preferably, the fibers contain less than 5% water by weight of the fiber, more preferably less than 3%, even more preferably less than 2%.
[0060] The fibers may be free of any surfactant. If it is desired that the surfactant is part of the article, the surfactant may be included in the fabric treatment composition, for example as part of a particulate laundry detergent composition. That said, the fibers may contain surfactants that may provide additional cleaning benefits in certain cases.
[0061] The fibers may further comprise a plasticizer and / or a pH adjuster.
[0062] The fibers may be made by any suitable process. The fibers may be spun from a filament-forming composition using techniques known to those skilled in the art, the filament-forming composition comprising a water-soluble polymer. Suitable spinning process operations may include meltblowing, spunbonding, electrospinning, rotary spinning, or combinations thereof.
[0063] Without wishing to be bound by theory, nonwoven fibrous sheets exhibit a different dissolution profile than cast sheets. The dissolution of fibrous nonwoven substrates can be tested according to the methods provided in the Test Methods section.
[0064] Non-limiting examples of suitable processes for making fibers include: a. providing a filament forming composition, such as from a tank; b. spinning the filament-forming composition into one or more fibers, such as through a spinning die; c. collecting the fibers on a collecting device, such as a patterned belt.
[0065] The filament-forming composition may be transported, with or without a pump, between the tank and the spinning die via suitable piping. The spinning die may include a plurality of fiber-forming holes that include molten capillaries surrounded by concentric attenuating fluid holes through which a fluid, such as air, passes to facilitate attenuation of the filament-forming composition into fibers as it exits the fiber-forming holes.
[0066] The filament-forming composition may be spun into one or more fibers by any suitable spinning process, such as meltblowing, spunbonding, electrospinning, and / or rotary spinning. The filament-forming composition may be spun into multiple fibers by meltblowing. For example, the filament-forming composition may be pumped from a tank to a meltblowing spinnerette. Upon exiting one or more fiber-forming holes in the spinnerette, the filament-forming composition is attenuated with air to create one or more fibers. The fibers may then be dried to remove any residual solvent, such as water, used in spinning.
[0067] The fibers may be collected on a belt, such as a pattern belt, to form a fibrous nonwoven sheet containing the fibers.
[0068] Preferably, fibrous nonwoven sheets are made by bonding or interlocking fibers by mechanical, thermal, chemical or solvent means. When fibrous nonwoven sheets are made from staple fibers, their manufacture involves forming a uniform web by wet-laid process or carding, followed by bonding the nonwoven fabric either by heat or other means such as needle punching, hydroentangling, etc. Spunlaid fibrous nonwoven fabrics are made in one continuous process where fibers are spun and then directly dispersed into a web by deflectors or air streams. Meltblown fibrous nonwoven fabrics are a one-step process where high-velocity air blows molten thermoplastic resin from the extruder die tip onto a conveyor or take-up screen to form a fine fibrous self-bonded web.
[0069] Additional disclosure regarding fibers, substrates, articles, and processes for making such materials can be found, for example, in U.S. Pat. No. 9,163,205 (equivalent: WO 2012 / 003316), and / or U.S. Pat. No. 9,074,305 (equivalent: WO 2012 / 003367), and / or U.S. Patent Application Publication No. 20190233974(A1), and / or U.S. Patent Application Publication No. 20190233970(A1), all of which are incorporated by reference.
[0070] Fabric Treatment Composition The water-soluble unit dose article according to the present disclosure comprises a fabric treatment composition. The fabric treatment composition is preferably a particulate fabric treatment composition. The fabric treatment composition of the present disclosure may be a laundry detergent composition, a laundry additive composition, or a combination thereof.
[0071] The main function of laundry detergent compositions is typically to remove dirt from fabrics. Such detergent compositions typically contain a detersive surfactant, such as an anionic surfactant, at a concentration sufficient to provide a dirt removal effect. The laundry detergent composition may contain a detersive surfactant, preferably an anionic surfactant, at a concentration of more than 5% by weight, preferably more than 10% by weight of the treatment composition. When the fabric treatment composition is a detergent composition, it may be preferable to use a unit dose article during a washing operation, for example during a wash cycle in an automatic washing machine.
[0072] The main function of laundry additive compositions is typically to provide alternative or additional benefits other than soil removal. For example, the additive composition may provide conditioning / softening benefits, freshness and / or malodor removal benefits, etc. The laundry additive composition may have a relatively low detergent surfactant content, for example, less than 5%, less than 3%, or even less than 1% by weight of the treatment composition. When the fabric treatment composition is an additive composition, it may be used in the washing operation and / or rinsing operation, preferably during the rinsing operation, for example during the rinse cycle in an automatic washing machine.
[0073] Typically, the particles of the composition can be prepared by any suitable method, such as agglomeration, extrusion, or any combination thereof. Typically, the agglomerates are subjected to particle size classification, e.g., fluidized bed elutriation and / or sieving, to obtain the desired particle size distribution. Preferably, the agglomerates have a weight average particle size in the range of 300 micrometers to 800 micrometers, with less than 10% by weight of the agglomerates having a particle size less than 150 micrometers and less than 10% by weight of the agglomerates having a particle size greater than 1200 micrometers.
[0074] The fabric treatment compositions of the present disclosure include certain capsules and optional adjunct ingredients, which are described in more detail below.
[0075] capsule The treatment composition of the present disclosure includes a capsule. The capsule typically exists as a mass of capsules. The capsule includes a core and a shell surrounding the core. As described in more detail below, the core includes a benefit agent, preferably a fragrance, and the shell includes an inorganic material.
[0076] The capsules may be present in the treatment composition in an amount of about 0.05% to about 20%, or about 0.05% to about 10%, or about 0.1% to about 5%, or about 0.2% to about 2% by weight of the composition. The composition may include a sufficient amount of total capsules to provide the treatment composition with about 0.05% to about 10%, or about 0.1% to about 5%, or about 0.1% to about 2% of a benefit agent, preferably a fragrance, by weight of the composition. As discussed herein, the amount or weight percentage of capsules refers to the combined shell material and core material.
[0077] The capsules may have an average shell thickness of from 10 nm to 10,000 nm, preferably from 170 nm to 1000 nm, and more preferably from 300 nm to 500 nm.
[0078] The capsules may have an average volume-weighted capsule diameter of from 0.1 micrometers to 300 micrometers, preferably from 5 micrometers to 250 micrometers, more preferably from 10 micrometers to 200 micrometers, and even more preferably from 10 micrometers to 50 micrometers.
[0079] Surprisingly, it has been found that in addition to the inorganic shell, the volume core-to-shell ratio can also play an important role in ensuring the physical integrity of the capsule. Shells that are too thin relative to the overall capsule size (core-to-shell ratio >98:2) tend to suffer from lack of self-integrity. On the other hand, shells that are too thick relative to the capsule diameter (core-to-shell ratio <80:20) tend to have higher shell permeability in surfactant-rich matrices. While it would be intuitive to think that a thicker shell would result in a lower shell permeability (because this parameter affects the average diffusion path of the active substance across the shell), it has been surprisingly found that capsules of the present invention with a shell having a thickness above a threshold value have higher shell permeability. This upper threshold value is believed to depend to some extent on the capsule diameter. The volume core-to-shell ratio is determined according to the method provided in the Test Methods section below.
[0080] The capsules may have a volume core to shell ratio of 50:50 to 99:1, preferably 60:40 to 99:1, preferably 70:30 to 98:2, more preferably 80:20 to 96:4.
[0081] It may be desirable to have a particular combination of these capsule properties. For example, the capsules can have a volumetric core-to-shell ratio of about 99:1 to about 50:50, an average volume-weighted capsule diameter of about 0.1 μm to about 200 μm, and an average shell thickness of about 10 nm to about 10,000 nm. The capsules can have a volumetric core-to-shell ratio of about 99:1 to about 50:50, an average volume-weighted capsule diameter of about 10 μm to about 200 μm, and an average shell thickness of about 170 nm to about 10,000 nm. The capsules can have a volumetric core-to-shell ratio of about 98:2 to about 70:30, an average volume-weighted capsule diameter of about 10 μm to about 100 μm, and an average shell thickness of about 300 nm to about 1000 nm.
[0082] The method of the present disclosure can produce capsules with a low coefficient of variation in capsule diameter. Controlling the distribution of capsule sizes can improve the breaking strength of the population and allow the population to have a more uniform breaking strength. The capsule population can have a coefficient of variation in capsule diameter of 40% or less, preferably 30% or less, and more preferably 20% or less.
[0083] The capsules described herein can have an average breaking strength of 0.1 MPa to 10 MPa, preferably 0.25 MPa to 5 MPa, and more preferably 0.25 MPa to 3 MPa. Fully inorganic capsules traditionally have poor breaking strength, but the capsules described herein can have a breaking strength of greater than 0.25 MPa, improving stability and allowing the release of beneficial agent to be triggered upon application of a specified amount of burst stress.
[0084] In certain embodiments, it may be preferred that the capsules have an average volume-weighted diameter of 1 to 200 micrometers, preferably 1 to 10 micrometers, and even more preferably 2 to 8 micrometers. It may be preferred that the shell thickness is 1 to 10,000 nm, preferably 1 to 1000 nm, and more preferably 10 to 200 nm. In further embodiments, it may be preferred that the capsules have an average volume-weighted diameter of 1 to 10 micrometers and a shell thickness of 1 to 200 nm. It has been found that capsules having an average volume-weighted diameter of 1 to 10 micrometers and a shell thickness of 1 to 200 nm may have a higher breaking strength.
[0085] In general, smaller capsules may be relatively stronger and therefore may be preferred. Without wishing to be bound by theory, it is believed that a higher breaking strength provides better survivability during the washing process, as due to mechanical constraints in the washing machine, this process may cause premature rupture of mechanically weak capsules.
[0086] It is believed that capsules having an average volume weighted diameter of 1-10 micrometers and a shell thickness of 10-200 nm may provide resistance to mechanical constraints, especially when made with a careful selection of the silica precursor used. It may be preferred that the precursor has a molecular weight of 2-5 kDa, and even more preferably a molecular weight of 2.5-4 kDa. In addition, the concentration of the precursor may be carefully selected, for example, so that the concentration is 20-60% by weight, preferably 40-60% by weight, of the oil phase used during the encapsulation process.
[0087] Without being bound by theory, it is believed that higher molecular weight precursors have a much slower migration time from the oil phase to the water phase. The slower migration time is believed to result from a combination of three phenomena: diffusion, partitioning, and reaction kinetics. This phenomenon may be important in the context of small capsules, for example, due to the fact that the total surface area between the oil and water in the system increases as the capsule diameter decreases. A larger surface area may result in a larger migration of precursors from the oil phase to the water phase, which in turn may reduce the yield of polymerization at the interface. Therefore, a higher molecular weight precursor may be useful to mitigate the effects caused by the increased surface area and obtain capsules according to the present disclosure.
[0088] The capsules may be characterized by one or more of the following: (a) an average volume-weighted capsule diameter of about 1 μm to about 250 μm, preferably about 4 μm to about 225 μm, and more preferably 10 μm to about 200 μm; (b) an average shell thickness of about 170 nm to about 1000 nm; (c) a volumetric core-to-shell ratio of about 50:50 to about 99:1; (d) the first shell component comprises an organic component content of about 5% by weight or less, based on the weight of the first shell component; or (e) mixtures thereof.
[0089] The capsule core and shell are described in more detail below.
[0090] core The capsule core comprises a benefit agent. The benefit agent is preferably a hydrophobic material. The core may be oil-based or the core may be water-based. Preferably, the core is oil-based. The core may be liquid at the temperature at which the core is to be used in the formulated product. The core may be liquid at or near room temperature.
[0091] The core comprises a flavoring. The core may comprise about 1% to 100% by weight of flavoring based on the total weight of the core. Preferably, the core may comprise 50% to 100% by weight of flavoring based on the total weight of the core, more preferably 80% to 100% by weight of flavoring based on the total weight of the core. Typically, a higher concentration of flavoring is preferred for improved delivery efficiency.
[0092] A perfume may comprise one or more, preferably two or more, perfume raw materials. The term "perfume raw material" (or perfume raw material, "PRM"), as used herein, means a compound having a molecular weight of at least about 100 g / mole and useful for imparting an odor, fragrance, essence, or scent, alone or together with other perfume raw materials. Typical PRMs include, among others, alcohols, ketones, aldehydes, esters, ethers, nitrites, and alkenes such as terpenes. Lists of common PRMs can be found in various reference sources, such as, for example, "Perfume and Flavor Chemicals" Vol. I and Vol. II; Steffen Arctander Allured Pub.Co. (1994) and "Perfumes: Art, Science and Technology", Miller, PM and Lamparsky, D., Blackie Academic and Professional (1994).
[0093] PRMs may be characterized by their boiling point (BP) measured at normal pressure (760 mmHg) and octanol / water partition coefficient (P), which may be described in terms of logP determined according to the test methods described in the Test Methods section. Based on these characteristics, PRMs may be classified as Quadrant I, Quadrant II, Quadrant III, or Quadrant IV perfumes, as described in more detail below. Perfumes with various PRMs from different quadrants may be desirable, for example, to provide fragrance benefits at different touch points during normal use.
[0094] Perfume raw materials having a boiling point BP below about 250°C and a logP below about 3 are known as quadrant I perfume raw materials. Quadrant 1 perfume raw materials are preferably limited to less than 30% of the perfume composition. Perfume raw materials having a BP above about 250°C and a logP above about 3 are known as quadrant IV perfume raw materials, perfume raw materials having a BP above about 250°C and a logP below about 3 are known as quadrant II perfume raw materials, and perfume raw materials having a BP below about 250°C and a logP above about 3 are known as quadrant III perfume raw materials. Suitable quadrant 1, quadrant 2, quadrant 3 and quadrant 4 perfume raw materials are disclosed in U.S. Patent No. 6,869,923(B1).
[0095] The perfume microcapsules contain perfume. Preferably, the perfume of the microcapsules contains a mixture of at least 3, or even at least 5, or at least 7 perfume raw materials. The perfume of the microcapsules may contain at least 10 or at least 15 perfume raw materials. A mixture of perfume raw materials may provide more complex and desirable aesthetics and / or better perfume performance or longevity, for example, at various touch points. However, it may be desirable to limit the number of perfume raw materials in a perfume to reduce or limit the complexity and / or cost of formulation.
[0096] The perfume may include at least one perfume raw material of natural origin. Such ingredients may be desirable for sustainability / environmental reasons. The perfume raw material of natural origin may include natural extracts or essences that may contain a mixture of PRMs. Such natural extracts or essences may include orange oil, lemon oil, rose extract, lavender, musk, patchouli, balsam essence, sandalwood oil, pine oil, cedar, etc.
[0097] In addition to the perfume raw material, the core may contain a pro-perfume, which may contribute to improving the longevity of the freshness effect. The pro-perfume may, for example, comprise a non-volatile substance that releases or converts a perfume material into a perfume material as a result of simple hydrolysis, or may be a pH-change-triggered pro-perfume (e.g., triggered by a pH drop), or an enzymatically releasable pro-perfume, or a light-triggered pro-perfume. The pro-perfume may exhibit different release rates depending on the pro-perfume selected.
[0098] The core of the encapsulation of the present disclosure may include a core modifier, such as a partitioning modifier and / or a density modifier. In addition to the flavoring, the core may include from greater than 0% to about 80%, preferably from greater than 0% to about 50%, more preferably from greater than 0% to about 30% of the core modifier based on the total weight of the core. The partitioning modifier may be vegetable oil, modified vegetable oil, C4-C 24 The partitioning modifier may comprise a material selected from the group consisting of mono-, di-, and triesters of fatty acids, isopropyl myristate, dodecanophenone, lauryl laurate, methyl behenate, methyl laurate, methyl palmitate, methyl stearate, and mixtures thereof. The partitioning modifier may preferably comprise or consist of isopropyl myristate. The modified vegetable oil may be esterified and / or brominated. The modified vegetable oil may preferably comprise castor oil and / or soybean oil. US Patent Publication No. 20110268802, incorporated herein by reference, describes other partitioning modifiers that may be useful in the perfume encapsulation agents described herein.
[0099] shell The capsules of the present disclosure include a shell surrounding the core. The shell includes an inorganic material. The capsule shell may include about 90% to about 100% inorganic material by weight of the shell.
[0100] The inorganic material in the shell comprises a material selected from metal oxides, semi-metal oxides, metals, minerals, or mixtures thereof. Preferably, the inorganic material in the shell is a material selected from SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, clay, gold, silver, iron, nickel, copper, or mixtures thereof, more preferably SiO2.
[0101] The shell may include a first shell component. The shell may preferably include a second shell component surrounding the first shell component. The first shell component may include a condensation layer formed from a condensation product of a precursor. As described in detail below, the precursor may include one or more precursor compounds. The first shell component may include a nanoparticle layer. The second shell component may include an inorganic material.
[0102] The shell may be substantially inorganic (as defined below). The substantially inorganic shell may include a first shell component including a condensed layer surrounding the core, and may further include a nanoparticle layer surrounding the condensed layer. The substantially inorganic shell may further include a second shell component surrounding the first shell component. The first shell component includes an inorganic material, preferably a metal / metalloid oxide, more preferably SiO2, TiO2 and Al2O3, even more preferably SiO2. The second shell component includes an inorganic material, preferably a material from the group of metal / metalloid oxides, metals, and minerals, more preferably a material selected from the list of SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, clay, gold, silver, iron, nickel, and copper, or mixtures thereof, even more preferably a material selected from SiO2 and CaCO3 or mixtures thereof. Preferably, the material of the second shell component is of the same chemical type as the first shell component to maximize chemical compatibility.
[0103] The first shell component can include a condensation layer surrounding the core. The condensation layer can include a condensation product of one or more precursors. The one or more precursors can include at least one compound from the group consisting of formula (I), formula (II), and mixtures thereof, where formula (I) is (M v O z Y n ) w and formula (II) is (M v O z Y n R 1 p ) w The precursor may contain only compounds according to formula (I) and not compounds according to formula (II) (i.e., R 1 Formulae (I) and (II) are described in more detail below.
[0104] The one or more precursors may be of formula (I): (M v O z Y n ) w (Formula I) In the formula, M is at least one of silicon, titanium, and aluminum, v is the valence of M and is 3 or 4, z is 0.5 to 1.6, preferably 0.5 to 1.5, and each Y is -OH, -OR 2 , -NH2, -NHR 2 , -N(R 2 )2, and R 2 is C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S; R 3 H, C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S, n is 0.7-(v-1), and w is 2-2000.
[0105] The one or more precursors may be of formula (I), where M is silicon. Y is -OR 2 n may be 1 to 3. Y may be -OR 2 and n is preferably 1 to 3. n is at least 2, and one or more of Y's are -OR 2 and one or more of Y's may preferably be -OH.
[0106] R 2 is C1~C 20 R may be alkyl. 2 is C6~C 22 R may be aryl. 2 R may be one or more of C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl, and C8 alkyl. 2 R may be C1 alkyl. 2 R may be a C2 alkyl. 2 may be a C3 alkyl. 2 may be a C4 alkyl.
[0107] z may be from 0.5 to 1.3, from 0.5 to 1.1, from 0.5 to 0.9, from 0.7 to 1.5, from 0.9 to 1.3, or from 0.7 to 1.3.
[0108] M is silicon, v is 4, and each Y is -OR 2 where n is 2 and / or 3, and each R 2 may be a C2 alkyl.
[0109] The precursors can include polyalkoxysilanes (PAOS). The precursors can include polyalkoxysilanes (PAOS) synthesized via a non-hydrolytic process.
[0110] The precursor may alternatively or additionally comprise one or more compounds of formula (II). (Mv O z Y n R 1 p ) w (Formula II) In the formula, M is at least one of silicon, titanium, and aluminum, v is the valence of M and is 3 or 4, z is 0.5 to 1.6, preferably 0.5 to 1.5, and each Y is -OH, -OR 2 , -NH2, -NHR 2 , -N(R 2 )2, and R 2 is C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S; R 3 H, C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or a 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S, n is 0-(v-1), and each R 1 is C1~C 30 Alkyl; C1-C 30 alkylene; C1-C substituted with a member (e.g., one or more) selected from the group consisting of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, -C(O)OH, -C(O)O-alkyl, -C(O)O-aryl, -C(O)O-heteroaryl, and mixtures thereof. 30 alkyl; and C1-C substituted with a member selected from the group consisting of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, -C(O)OH, -C(O)O-alkyl, -C(O)O-aryl, and -C(O)O-heteroaryl. 30 alkylene, p is a number from 0 to pmax, and pmax=60 / [9 * Mw(R1 )+8], and Mw(R 1 ) is R 1 is the molecular weight of the group, and w is 2 to 2,000.
[0111] R 1 is a C1-C substituted with 1 to 4 groups independently selected from halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H (i.e., C(O)OH), -C(O)O-alkyl, -C(O)O-aryl, and -C(O)O-heteroaryl; 30 R may be alkyl. 1 is a C1-C substituted with 1 to 4 groups independently selected from halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, C(O)O-alkyl, C(O)O-aryl, and C(O)O-heteroaryl; 30 It may be an alkylene.
[0112] As noted above, it may be preferable to reduce or even eliminate the presence of compounds according to formula (II) having R groups in order to reduce or even eliminate the organic content in the first shell component. The precursor, the condensation layer, the first shell component, and / or the shell may be free of compounds according to formula (II).
[0113] The precursors of formula (I) and / or (II) may be characterized by one or more physical properties, namely molecular weight (Mw), degree of branching (DB) and polydispersity index (PDI) of molecular weight distribution. It is believed that selecting a particular Mw and / or DB may be useful to obtain capsules that retain their mechanical integrity when dried on a surface and have low shell permeability in a surfactant-based matrix. The precursors of formula (I) and (II) may be characterized by having a DB of 0 to 0.6, preferably 0.1 to 0.5, more preferably 0.19 to 0.4, and / or a Mw of 600 Da to 100,000 Da, preferably 700 Da to 60,000 Da, more preferably 1,000 Da to 30,000 Da. The characteristics provide useful properties of the precursors to obtain the capsules of the present invention. The precursors of formula (I) and / or (II) may have a PDI of 1 to 50.
[0114] The condensation layer comprising a metal / semi-metal oxide may be formed from a condensation product of a precursor comprising at least one compound of formula (I) and / or at least one compound of formula (II), optionally in combination with one or more monomeric precursors of a metal / semi-metal oxide, including TiO2, Al2O3 and SiO2, preferably SiO2. Monomeric precursors of a metal / semi-metal oxide include compounds of formula M(Y) V-n R n (wherein M, Y, and R are as defined in formula (II) and n can be an integer from 0 to 3). The monomer precursor of the metal / semi-metal oxide is preferably a compound of the general formula Si(Y) 4-n R n(wherein Y and R are defined as in formula (II), and n can be an integer from 0 to 3.) Examples of such monomers are TEOS (tetraethoxyorthosilicate), TMOS (tetramethoxyorthosilicate), TBOS (tetrabutoxyorthosilicate), triethoxymethylsilane (TEMS), diethoxy-dimethylsilane (DEDMS), trimethylethoxysilane (TMES), and tetraacetoxysilane (TAcS). These are not intended to limit the scope of monomers that can be used, and suitable monomers that can be used in combination herein will be apparent to one of ordinary skill in the art.
[0115] The first shell component can include an optional nanoparticle layer. The nanoparticle layer includes nanoparticles. The nanoparticles of the nanoparticle layer can be one or more of SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, clay, silver, gold, and copper. Preferably, the nanoparticle layer can include SiO2 nanoparticles.
[0116] The nanoparticles can have an average diameter of from 1 nm to 500 nm, preferably from 50 nm to 400 nm.
[0117] The size of the capsule pores can be adjusted by changing the shape of the nanoparticles and / or by using a combination of nanoparticles of different sizes. For example, non-spherical and irregular nanoparticles can be used as they may improve the packing when forming the nanoparticle layer, thereby resulting in a denser shell structure. This may be advantageous when permeability needs to be limited. The nanoparticles used can have a more regular shape, such as spherical. Any conceivable nanoparticle shape can be used herein.
[0118] The nanoparticles may be substantially free of hydrophobic modifications. The nanoparticles may be substantially free of organic compound modifications. The nanoparticles may include organic compound modifications. The nanoparticles may be hydrophilic.
[0119] The nanoparticles may include surface modifications, examples of which include linear or branched C1-C 20 These surface modifications include, but are not limited to, alkyl groups, surface amino groups, surface methacryl groups, surface halogens, or surface thiols. These surface modifications allow the nanoparticle surface to have organic molecules covalently attached thereto. When inorganic nanoparticles are disclosed herein for use, this means that they may or may not include any of the above surface modifications, even if not explicitly listed.
[0120] The capsule of the present disclosure may be defined as comprising a substantially inorganic shell, comprising a first shell component and a second shell component. Substantially inorganic means that the first shell component may comprise up to 10% by weight, or up to 5% by weight, preferably up to 1% by weight, as defined below in the calculation of organic content. It may be preferred that the first shell component, the second shell component, or both, in some cases, comprise an organic content of about 5% by weight or less, preferably about 2% by weight or less, more preferably about 0% by weight, based on the weight of the first or shell component.
[0121] The first shell component is useful for building a mechanically robust scaffold or skeleton, but can also provide low shell permeability in liquid products containing surfactants, such as laundry detergents, shower gels, cleansers, etc. (see Surfactants in Consumer Products, J. Falbe, Springer-Verlag). The second shell component can significantly reduce shell permeability improving capsule impermeability in surfactant-based matrices. The second shell component can also significantly improve capsule mechanical properties, such as capsule burst force and crush strength. Without being bound by theory, it is believed that the second shell component contributes to the overall shell densification by depositing precursors in the remaining pores in the first shell component. The second shell component also adds an additional inorganic layer on the surface of the capsule. These improved shell permeability and mechanical properties provided by the second shell component only occur when used in combination with the first shell component as defined in the present invention.
[0122] Additional description of shell structures, their materials, and how they interact with each other to provide optimal performance, and methods for making the capsules of the present disclosure can be found in U.S. Patent Application Nos. 16 / 851,173, 16 / 851,176, and 16 / 851,194, the disclosures of which are incorporated herein by reference in their entireties.
[0123] How to make a capsule The capsules of the present disclosure may be formed by first mixing a hydrophobic material with any of the above-defined precursors of the condensed layer, thereby forming an oil phase, which may include oil-based and / or oil-soluble precursors. The mixture of precursors and hydrophobic material is then used as a dispersed phase or as a continuous phase with an aqueous phase. When the two phases are mixed and homogenized via methods known to those skilled in the art, an O / W (oil-in-water) emulsion is formed in the former case, and a W / O (water-in-oil) emulsion is formed in the latter case. Preferably, an O / W emulsion is formed. The nanoparticles can be present in the aqueous phase and / or the oil phase, regardless of the type of emulsion desired. The oil phase may include an oil-based core conditioning agent and / or an oil-soluble benefit agent as well as the precursors of the condensed layer. Suitable core materials used in the oil phase are described herein above.
[0124] Once either emulsion is formed, the following can occur: (a) Nanoparticles migrate to the oil / water interface, thereby forming a nanoparticle layer. (b) The precursors of the condensation layer, including precursors of metal / metalloid oxides, begin to undergo hydrolysis / condensation reactions with water at the oil / water interface, thus forming a condensation layer surrounded by the nanoparticle layer. The precursors of the condensation layer can further react with the nanoparticles of the nanoparticle layer.
[0125] The precursors forming the condensation layer may be present in an amount of from 1% to 50% by weight, preferably from 10% to 40% by weight, based on the total weight of the oil phase.
[0126] The oil phase composition may contain any of the compounds defined in the core section above. The oil phase may contain from 10% to about 99% by weight of the benefit agent prior to emulsification.
[0127] In the method of making capsules according to the present disclosure, the oil phase may be the dispersed phase and the continuous aqueous (or water) phase may comprise water, an acid or base, and nanoparticles. The aqueous phase (or water) may have a pH of 1-11, preferably 1-7, at least at the time of mixing both the oil and water phases together. The acid may be a strong acid. The strong acid may comprise one or more of HCl, HNO3, H2SO4, HBr, HI, HClO4, and HClO3, preferably HCl. The acid may be a weak acid. The weak acid may be acetic acid or HF. The concentration of the acid in the continuous aqueous phase may be from 10 to 150°C. -7 The base may be a mineral base or an organic base, preferably an inorganic base. The mineral base may be a hydroxide, such as sodium hydroxide, and ammonia. For example, the mineral base may be about 10 -5 0.01 μM NaOH, or about 10 -5 The above list of exemplary acids and bases and their concentration ranges is not meant to limit the scope of the invention, and other suitable acids and bases that allow for control of the pH of the continuous phase are contemplated herein.
[0128] In the method of making capsules according to the present disclosure, the pH can be varied throughout the process by adding acid and / or base. For example, the method can start with an aqueous phase of acidic or neutral pH, and then a base can be added during the process to increase the pH. Alternatively, the method can start with an aqueous phase of basic or neutral pH, and then an acid can be added during the process to decrease the pH. Furthermore, the method can start with an aqueous phase of acidic or neutral pH, and then an acid can be added during the process to further decrease the pH. Still further, the method can start with an aqueous phase of basic or neutral pH, and then a base can be added during the process to further increase the pH. Any suitable pH shift may be used. Furthermore, any suitable combination of acid and base may be used at any time to achieve the desired pH. Any of the nanoparticles described above may be used in the aqueous phase. The nanoparticles may be present in an amount of about 0.01% to about 10% by weight, based on the total weight of the aqueous phase.
[0129] The method can include mixing an oil phase and an aqueous phase in a ratio of about 1:10 to about 1:1 of oil to aqueous phase.
[0130] The second shell component can be formed by mixing the capsules having the first shell component with a solution of a second shell component precursor. The solution of the second shell component precursor can include a water-soluble or oil-soluble second shell component precursor. The second shell component precursor can be one or more of the compounds of formula (I) defined above, tetraethoxysilane (TEOS), tetramethoxysilane (TMOS), tetrabutoxysilane (TBOS), triethoxymethylsilane (TEMS), diethoxy-dimethylsilane (DEDMS), trimethylethoxysilane (TMES), and tetraacetoxysilane (TAcS). The second shell component precursor can be Si(Y) 4-n R nThe second shell component precursor may also include one or more of the following silane monomers: (wherein Y is a hydrolyzable group, R is a non-hydrolyzable group, and n may be an integer from 0 to 3). Examples of such monomers are described above in this paragraph, but they are not meant to limit the scope of monomers that may be used. The second shell component precursor may include silicates, titanates, aluminates, zirconates, and / or zincates. The second shell component precursor may include carbonates and calcium salts. The second shell component precursor may include iron, silver, copper, nickel, and / or gold salts. The second shell component precursor may include zinc, zirconium, silicon, titanium, and / or aluminum alkoxides. The second shell component precursor may include one or more of the following silicate solutions, for example, sodium silicate, silicon tetraalkoxide solutions, iron sulfates and nitrates, titanium alkoxide solutions, aluminum trialkoxide solutions, zinc dialkoxide solutions, zirconium alkoxide solutions, calcium salt solutions, and carbonate solutions. The second shell component containing CaCO3 can be obtained from the combined use of calcium salts and carbonate salts. The second shell component containing CaCO3 can be obtained from calcium salts without the addition of carbonate salts, which requires the in situ generation of carbonate ions from CO2.
[0131] The second shell component precursor may include any suitable combination of any of the aforementioned compounds.
[0132] The solution of the second shell component precursor can be added dropwise to the capsule containing the first shell component. The solution of the second shell component precursor and the capsule can be mixed together for 1 minute to 24 hours. The solutions of the second shell component precursor and the capsule can be mixed together at room temperature or at an elevated temperature, for example, 20°C to 100°C.
[0133] The second shell component precursor solution can include the second shell component precursor in an amount of 1 wt % to 50 wt % based on the total weight of the second shell component precursor solution.
[0134] The capsules having the first shell component can be mixed with a solution of the second shell component precursor at a pH of 1-11. The solution of the second shell precursor can contain an acid and / or a base. The acid can be a strong acid. The strong acid can include one or more of HCl, HNO3, H2SO4, HBr, HI, HClO4, and HClO3, preferably HCl. In other embodiments, the acid can be a weak acid. In embodiments, the weak acid can be acetic acid or HF. The concentration of the acid in the second shell component precursor solution can be between 10 and 11. -7 The base may be a mineral base or an organic base, preferably a mineral base. The mineral base may be a hydroxide, such as sodium hydroxide, and ammonia. For example, the mineral base may be about 10 -5 0.01 μM NaOH, or about 10 -5 The above list of exemplary acids and bases is not meant to limit the scope of the invention, and other suitable acids and bases that allow for control of the pH of the second shell component precursor solution are contemplated herein.
[0135] The process of forming the second shell component may include changing the pH during the process. For example, the process of forming the second shell component may start at an acidic or neutral pH, and then a base may be added during the process to increase the pH. Alternatively, the process of forming the second shell component may start at a basic or neutral pH, and then an acid may be added during the process to decrease the pH. Still further, the process of forming the second shell component may start at an acidic or neutral pH, and then an acid may be added during the process to further decrease the pH. Still further, the process of forming the second shell component may start at a basic or neutral pH, and then a base may be added during the process to further increase the pH. Any suitable pH shift may be used. Furthermore, any suitable combination of acid and base may be used in the solution of the second shell component precursor at any time to achieve the desired pH. The process of forming the second shell component may include maintaining a stable pH during the process, with a deviation of up to ±0.5 pH units. For example, the process of forming the second shell component may be maintained at a basic, acidic, or neutral pH. Alternatively, the process of forming the second shell component can be maintained at a particular pH range by controlling the pH using an acid or a base. Any suitable pH range may be used. Furthermore, any suitable combination of acid and base can be used in the solution of the second shell component precursor at any time to keep the pH stable in the desired range.
[0136] Whether making an oil-based or aqueous core, the emulsion can be cured under conditions that solidify the precursors, thereby forming a shell surrounding the core.
[0137] The reaction temperature for curing can be increased to increase the rate at which solidified capsules are obtained. The curing process can induce condensation of the precursors. The curing process can be carried out at room temperature or at a temperature higher than room temperature. The curing process can be carried out at a temperature between 30°C and 150°C, preferably between 50°C and 120°C, more preferably between 80°C and 100°C. The curing process can be carried out for any suitable period of time to allow the shell of the capsule to be strengthened through condensation of the precursor materials. The curing process can be carried out for a period of 1 minute to 45 days, preferably between 1 hour and 7 days, more preferably between 1 hour and 24 hours. A capsule is considered to be cured when it no longer disintegrates. The determination of capsule disintegration is described in detail below. During the curing process, hydrolysis of the Y moiety (from formula (I) and / or (II)) is believed to occur, followed by subsequent condensation of either the -OH group with another -OH group, or the -OH group with another moiety of the Y type (where the two Ys are not necessarily the same). The hydrolyzed portions of the precursor first condense with surface moieties of the nanoparticles (if the nanoparticles contain such moieties), and as the formation of the shell proceeds, the precursor moieties become reactive with the previously formed shell.
[0138] The emulsion can be cured such that the shell precursors react with the nanoparticles and condense. Below is an example of the hydrolysis and condensation steps described herein for a silica-based shell.
[0139]
number
[0140] For example, when a precursor of formula (I) or (II) is used, the following describes the hydrolysis and condensation steps.
[0141]
number
[0142] The capsules may be provided as a slurry composition (or simply "slurry" herein). The result of the methods described herein may be a slurry containing the capsules. The slurry may be formulated into a product, such as, for example, a consumer product.
[0143] The capsules may be freeze-dried. Such a preparation method may be preferred when the capsules are intended to be incorporated into a dry processing composition, such as the particulate processing composition of the present disclosure.
[0144] FIG. 4 shows a schematic diagram of a method for making a capsule (6). The capsule (6) may have a first shell component (10) prepared with a hydrophobic core (11). For example, in a first box (100), an oil phase (12) is provided to an aqueous phase (13). The aqueous phase (13) includes the oil phase (12), a hydrophobic benefit agent, such as one or more perfume raw materials, and a liquid precursor material. Nanoparticles (14) surround the oil phase (12), forming, for example, a Pickering emulsion. In a second box (101), hydrolyzed precursors (15) begin to form at the interface around the core (11), which includes the oil phase including the benefit agent. In a third box (102), the first shell component (10) is formed around the core (11), the first shell component being formed from the nanoparticles (14) and the hydrolyzed precursors (15).
[0145] Figure 5 shows a schematic diagram of a capsule (6) having a shell (16) in a box (103) with a first shell component (10) and a second shell component (17) around a core (11). The capsule (6) is shown in an aqueous phase (13). The core (11) contains one or more perfume raw materials.
[0146] Auxiliary substances In addition to the capsules described above, the treatment composition may include auxiliary materials. Such materials should be suitable for inclusion in the particulate fabric treatment composition. The selection of auxiliary materials may depend on whether the treatment composition is a laundry detergent composition or a laundry additive composition.
[0147] Adjuncts suitable for laundry detergent compositions may include detersive surfactants such as anionic detersive surfactants, nonionic detersive surfactants, cationic detersive surfactants, zwitterionic detersive surfactants and amphoteric detersive surfactants; polymers such as carboxylate polymers, soil release polymers, anti-redeposition polymers, cellulosic polymers and care polymers; bleaching agents such as hydrogen peroxide sources, bleach activators, bleach catalysts and preformed peracids; photobleaches such as zinc and / or aluminium sulfonated phthalocyanines and the like; enzymes such as proteases, amylases, cellulases, lipases; zeolite builders; phosphate builders; co-builders such as citric acid and citrates; carbonates such as sodium carbonate and sodium bicarbonate; sulfates such as sodium sulfate; silicates such as sodium silicate; chlorides such as sodium chloride; brighteners, chelating agents; hueing agents; dye transfer inhibitors; dye fixatives; fragrances; silicones; fabric softeners such as clays; flocculating agents such as polyethylene oxide; suds suppressors; and any combination thereof.
[0148] Suitable laundry detergent compositions may have a low buffering capacity. Such laundry detergent compositions typically have a reserve alkalinity of less than 5.0 g NaOH / 100 g up to pH 9.5. These low buffer laundry detergent compositions typically contain low concentrations of carbonate salts.
[0149] The particulate laundry detergent composition may comprise from 1% to 50% by weight of a surfactant system. Suitable detersive surfactants include anionic detersive surfactants, nonionic detersive surfactants, cationic detersive surfactants, zwitterionic detersive surfactants, and amphoteric detersive surfactants. Suitable detersive surfactants may be linear or branched, substituted or unsubstituted, and derived from petrochemicals or biomaterials.
[0150] The treatment composition may include an acid and / or a salt thereof. Preferably, the acid may include an organic acid and / or a salt thereof. Such acids (and their salts) may be particularly useful at high concentrations in laundry additive compositions, as they may provide conditioning benefits such as malodor reduction and / or softening.
[0151] The acid and / or salt thereof may be present in a concentration of about 10% to about 99% by weight of the particle treatment composition, preferably about 25% to about 99% by weight, more preferably about 50% to about 99% by weight, and even more preferably about 75% to about 99% by weight.
[0152] Preferred acids are selected from carboxylic acids. A highly preferred acid is citric acid. Preferred acids are C1-C 12 Carboxylic acids. C1~C 12 The term carboxylic acid refers to a carboxylic acid having 1 to 12 carbon atoms, including the C atom of the carboxyl group. The carboxylic acid may be a saturated hydrocarbon. Alternatively, the carboxylic acid may be an unsaturated hydrocarbon.
[0153] The carboxylic acid may be a cyclic carboxylic acid. An example of a cyclic carboxylic acid is a lactone, such as ascorbic acid. The carboxylic acid may be an aromatic carboxylic acid. An example of an aromatic carboxylic acid is salicylic acid.
[0154] Preferably, the carboxylic acid is at least a dicarboxylic acid. More preferably, it is at least a tricarboxylic acid. By at least a tricarboxylic acid, it is meant that it has at least three carboxyl groups.
[0155] Preferably, the carboxylic acid is a C4 to C8 carboxylic acid. In a preferred embodiment of the present invention, the carboxylic acid is selected from a C2 to C6 carboxylic acid.
[0156] Preferably, the acid is selected from the group consisting of acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, caproic acid, citric acid, succinic acid, hydroxysuccinic acid, maleic acid, fumaric acid, oxyacid, glyoxylic acid, adipic acid, lactic acid, tartaric acid, salicylic acid, ascorbic acid, salts thereof, and mixtures thereof. When salts are present, potassium, calcium and / or sodium salts are preferred.
[0157] The acid, particularly the carboxylic acid, such as citric acid, may be in the form of a salt. Preferably, the acid salt is a potassium, sodium, calcium, and / or sodium salt, more preferably a potassium or sodium salt, even more preferably a sodium salt. More preferably, the acid is a tripotassium and / or trisodium salt of a tricarboxylic acid. Most preferably, the acid is a tripotassium and / or trisodium salt of citric acid.
[0158] The acid may preferably be selected from citric acid, its salts, and mixtures thereof. More preferably, the acid is a mixture of citric acid and its salts, and even more preferably a mixture of citric acid and sodium citrate. It has been found that such materials can provide malodor control and / or conditioning benefits to fabrics.
[0159] It may be useful to select a particular weight ratio of the acid form to its salt form, for example to aid in controlling the pH. For example, the acid form and the salt form, preferably citric acid and sodium citrate, may be present in a weight ratio of about 1:1 to 1:0, preferably about 1:1 to about 20:1, preferably about 2:1 to about 15:1, preferably about 5:1 to about 10:1, more preferably about 6:1 to about 8:1.
[0160] The above acids and their salts are commercially available and their synthesis or isolation from sources is known to those skilled in the art.
[0161] The acid, preferably citric acid and / or its salts, is preferably in particulate form. The citric acid may include a coating. The coating may preferably be starch.
[0162] Treatment Method The present disclosure relates to methods of treating fabrics. Suitable fabrics may include clothing, towels, or linens.
[0163] The method may include combining water with a water soluble unit dose article according to the present disclosure to form a treatment solution, and contacting fabrics with the treatment solution, preferably in the drum of an automatic washing machine.
[0164] Generally, the treatment liquid is formed by dissolving the unit dose article in water, the resulting treatment liquid containing the treatment composition (preferably substantially dissolved or dispersed) and the water-soluble polymer of the water-soluble fibrous substrate that is intended to be dissolved as well.
[0165] The treatment liquid may be formed by diluting the water-soluble unit dose article with water 200 to 3000 times, preferably 300 to 2000 times.
[0166] The water used to make the treatment solution may be water of any hardness, preferably 0 gpg to 40 gpg. The treatment solution may be at a temperature of about 5°C to about 90°C, preferably about 10°C to about 60°C, more preferably about 12°C to about 45°C, and most preferably about 15°C to about 40°C.
[0167] The treatment liquor, preferably the rinse liquor, may be characterized by an acidic pH, preferably a pH less than about 6, more preferably about 2 to about 6, even more preferably about 3 to about 5.5, even more preferably about 4 to about 5. Such a pH profile may be useful in treating certain fabrics, particularly when a malodor reducing effect is desired. For example, the treatment composition may include an acid, and the pH of the treatment liquor may be relatively lower than the pH of the water used to make the treatment liquor as a result of the release of the acid from the unit dose article. The aqueous treatment liquor may have a pH at least 1 pH unit lower than the pH of the water. The incoming water may be substantially neutral or basic, while the resulting treatment liquor is acidic.
[0168] The treatment solution may comprise 0.01 to 100 ppm, preferably 0.1 to 10 ppm, of the water-soluble polymer, preferably polyvinyl alcohol, of the textile substrate. The treatment solution may comprise 1 to 1000 ppm, preferably 10 to 100 ppm, of the capsules. The capsules and the water-soluble polymer, preferably polyvinyl alcohol, may be present in the treatment solution in a weight ratio of preferably 1:1 to 100:1, preferably 10:1 to 50:1. It is believed that such a ratio helps to optimize performance benefits, for example, by facilitating attachment of the capsules to the target fabric.
[0169] The method may also include the step of contacting the fabric with the treatment solution, preferably in the drum of an automatic washing machine.
[0170] The contacting step may occur during the wash cycle of an automatic washing machine, which may be preferred when the treatment composition is a laundry detergent composition. In such cases, the unit dose article may be added directly to the drum or to the dispenser compartment of the automatic washing machine.
[0171] The contacting step may occur in the rinse cycle of an automatic washing machine, which may be preferred when the treatment composition is a laundry additive composition. In such cases, the unit dose article may preferably be added to the dispenser compartment of the automatic washing machine for convenient dispensing at the appropriate time.
[0172] Preferably, the treatment of the fabric during processing takes from 5 to 50 minutes to complete, preferably from 5 to 40 minutes, more preferably from 5 to 30 minutes, even more preferably from 5 to 20 minutes, and most preferably from 6 to 18 minutes.
[0173] combination Specifically contemplated combinations of the present disclosure are described herein in the following alphabetical sections, which are exemplary in nature and not intended to be limiting. A. A water soluble unit dose article comprising a water soluble fibrous nonwoven substrate and a particulate treatment composition, wherein the substrate comprises a plurality of fibers, the fibers comprise a water soluble polymer, the particulate treatment composition comprises a capsule, the capsule comprises a core and a shell surrounding the core, the core comprises a benefit agent, and the shell comprises an inorganic material. B. The water soluble unit dose article of paragraph A, wherein the water soluble fibrous nonwoven substrate has a basis weight of 20 gsm to 60 gsm, preferably 20 gsm to 55 gsm, more preferably 25 gsm to 50 gsm, and most preferably 25 gsm to 45 gsm. C. A water-soluble unit dose article described in any one of paragraphs A or B, wherein the water-soluble fibrous nonwoven substrate is in the form of a sheet molded to form at least one sealed internal compartment, and the treatment composition is contained in the sealed internal compartment. D. The water soluble unit dose article of any one of paragraphs A-C, wherein the capsule, preferably the treatment composition, is mixed with a plurality of fibers of a water soluble fibrous nonwoven substrate to form a coform structure. E. The water soluble unit dose article of any one of paragraphs A-D, wherein the water soluble polymer comprises polyvinyl alcohol, polyvinylpyrrolidone, starch, carboxymethyl cellulose, polyethylene oxide, derivatives thereof, or combinations thereof, preferably the water soluble polymer comprises polyvinyl alcohol, more preferably the polyvinyl alcohol polymer has a weight average molecular weight of from 5 kDa to 70 kDa, preferably from 7 kDa to 65 kDa, more preferably from 10 kDa to 60 kDa. F. The water soluble unit dose article of any one of paragraphs A-E, wherein the fiber further comprises a gel breaking agent, preferably the gel breaking agent is selected from a polyol, a sugar alcohol, an amine, an amide, a carbohydrate, a polyvalent cation, or a mixture thereof, more preferably a polyol, a sugar alcohol, or a mixture thereof, even more preferably a polyethylene glycol, glycerol, sorbitol, dipropylene glycol, and a mixture thereof, even more preferably a polyethylene glycol, preferably a polyethylene glycol characterized by a weight average molecular weight of 100-800, preferably 200-750, more preferably 400-700, even more preferably 500-650. G. The water soluble unit dose article of any one of paragraphs A-F, wherein the benefit agent comprises a fragrance. H. The water soluble unit dose article of any one of paragraphs A-G, wherein the capsule shell comprises from about 90% to about 100% inorganic material by weight of the shell. I. The water soluble unit dose article of any one of paragraphs A-H, wherein the inorganic material in the shell comprises a material selected from a metal oxide, a semi-metal oxide, a metal, a mineral, or a mixture thereof, preferably a material selected from SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, clay, gold, silver, iron, nickel, copper, or a mixture thereof. J. The water soluble unit dose article of any one of paragraphs A-I, wherein the shell comprises: (a) a first shell component comprising a condensation layer and a nanoparticle layer, wherein the condensation layer comprises a condensation product of precursors, and the nanoparticle layer comprises inorganic nanoparticles, the condensation layer being disposed between the core and the nanoparticle layer; and (b) a second shell component surrounding the first shell component, the second shell component surrounding the nanoparticle layer. K. The water soluble unit dose article of any one of paragraphs A-J, wherein the capsule is characterized by one or more of: an average volume weighted capsule diameter of about 1 μm to about 250 μm, preferably about 4 μm to about 225 μm, more preferably 10 μm to about 200; an average shell thickness of about 170 nm to about 1000 nm; a volumetric core to shell ratio of about 50:50 to about 99:1, and the first shell component comprises an organic component content of about 5% or less by weight, based on the weight of the first shell component; or a mixture thereof. L. the precursor comprises at least one compound selected from the group consisting of formula (I), formula (II), or a mixture thereof; Formula (I) is v O z Y n ) w and Formula (II) is v O z Y n R 1 p ) w and For formula (I), formula (II), or a mixture thereof: Each M is independently selected from the group consisting of silicon, titanium, and aluminum; v is the valency of M and is about 3 or about 4; z is about 0.5 to about 1.6; Each Y is -OH, -OR 2 ,halogen,
[0174] [ka] are independently selected from R 2 is C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl or a 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S; R 3 H, C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C22 aryl or a 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S; w is from about 2 to about 2000; For formula (I), n is 0.7 to (v-1); and For formula (II), n is 0 to (v-1); Each R 1 is C1~C 30 Alkyl; C1-C 30 alkylene; C1-C substituted with a member selected from the group consisting of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, -CO2H, -C(O)-alkyl, -C(O)O-aryl, and -C(O)O-heteroaryl. 30 alkyl; and C1-C substituted with a member selected from the group consisting of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, -C(O)OH, -C(O)O-alkyl, -C(O)O-aryl, and -C(O)O-heteroaryl. 30 alkylene; p is a number from 0 to pmax, pmax=60 / [9 * Mw(R 1 )+8], Mw(R 1 ) is R 1 The water-soluble unit dose article of paragraph J or K, wherein: M. The water soluble unit dose article of paragraph L, wherein, for Formula (I), Formula (II), or both, M is silicon. N. The water-soluble unit dose article of paragraph L or M, wherein one or both of the compounds of formula (I), formula (II), are characterized by one or more of: a polystyrene equivalent weight average molecular weight (Mw) of about 700 Da to about 30,000 Da; a degree of branching of about 0.2 to about 0.6; a molecular weight polydispersity index of about 1 to about 20; or a mixture thereof. O. The water soluble unit dose article of any one of paragraphs L-N, wherein for Formula (I), Formula (II), or both, Y is OR and R is selected from a methyl group, an ethyl group, a propyl group, or a butyl group, preferably an ethyl group. P. The water soluble unit dose article of any one of paragraphs J-O, wherein the inorganic nanoparticles of the first shell component comprise at least one of metal nanoparticles, mineral nanoparticles, metal oxide nanoparticles, or semi-metal oxide nanoparticles, or mixtures thereof, preferably, the inorganic nanoparticles comprise one or more materials selected from the group consisting of SiO2, TiO2, Al2O3, Fe2O3, Fe3O4, CaCO3, clay, silver, gold, copper, or mixtures thereof. Q. The water soluble unit dose article of any one of paragraphs J-P, wherein the second shell component comprises at least one of SiO2, TiO2, Al2O3, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, iron, silver, nickel, gold, copper, clay, or mixtures thereof. R. the particulate treatment composition further comprises from about 10% to about 99% by weight of the particulate treatment composition of an acid and / or a salt thereof; Preferred are acids selected from the group consisting of acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, caproic acid, citric acid, succinic acid, hydroxysuccinic acid, maleic acid, fumaric acid, oxylic acid, glyoxylic acid, adipic acid, lactic acid, tartaric acid, salicylic acid, ascorbic acid, salts thereof, and mixtures thereof. More preferably, the activator acid is selected from the group consisting of citric acid, its salts, and mixtures thereof; Even more preferably, the activator acid is a mixture of citric acid and sodium citrate; Preferably, the weight ratio of citric acid to sodium citrate is from about 1:1 to about 1:0, preferably from about 1:1 to about 20:1, preferably from about 2:1 to about 15:1, preferably from about 5:1 to about 10:1, more preferably from about 6:1 to about 8:1. S. The water soluble unit dose article of any one of paragraphs A-R, wherein the article further comprises a surfactant, wherein the surfactant is comprised in the fiber, the particulate treatment composition, or a combination thereof, preferably the surfactant is selected from the group consisting of anionic surfactants, nonionic surfactants, cationic surfactants, zwitterionic surfactants, amphoteric surfactants, ampholytic surfactants, and mixtures thereof. T. A method of treating fabrics, comprising combining water with a water soluble unit dose article described in any one of paragraphs A-S to form a treatment solution, and contacting the fabrics with the treatment solution, preferably in the drum of an automatic washing machine.
[0175] Test Method It will be understood that the values of each of the parameters of Applicant's claimed subject matter claimed and described herein should be determined using the test methods disclosed in the Test Methods section of this application.
[0176] Base material melting The following is a test method for measuring dissolution of fibrous nonwoven substrates. In an exemplary dissolution method, the following equipment can be used: 2000mL glass beaker (approximately 7.5" high x 5.5" diameter) Magnetic stirrer dish (Labline, Melrose Park, IL, Model No. 1250 or equivalent) Magnetic stir bar (2" long x 3 / 8" diameter, Teflon coated) Thermometer (1~100℃+ / -1℃) 1.25 inch paper binder clip Alligator clamp (approximately 1 inch long) Holder with depth adjustment rod and bottom A timer (with at least 0.1 second accuracy) Deionized water (equilibrated at 23°C ± 1°C) Punching Die - Stainless steel punching die measuring 3.8cm x 3.2cm Polaroid 35mm Slide Mount (available from Polaroid Corporation or equivalent) 35mm Slide Mount Holder (or equivalent)
[0177] The fibrous nonwoven sheet samples are equilibrated in a constant temperature and humidity environment of 23°C ± 1°C and 50% ± 2% relative humidity for at least 24 hours prior to testing. The dissolution test is also carried out under these temperature and relative humidity conditions.
[0178] The basis weight of the sample material is measured using known techniques.
[0179] Three dissolution test specimens are cut from the fibrous nonwoven sheet sample to be tested using a die cutter to fit within a 35 mm slide platform with hole area dimensions of 24 x 36 mm (3.8 cm x 3.2 cm).
[0180] Each sample is mounted on an individual 35 mm slide.
[0181] Place 1600 ± 5 mL of deionized water in a 2000 mL glass beaker and place on a magnetic stir plate. Place a magnetic stir bar in the bottom of the beaker. Adjust the stirring speed to create a steady vortex so that the bottom of the vortex is at the 1200 mL mark in the center of the beaker.
[0182] A test run may be required to ensure the depth adjustment rod is set correctly. Secure the 35mm slide base in the alligator clamp of the 35mm slide base holder so that the long end of the slide base is parallel to the water surface. The alligator clamp should be centered on the long end of the slide base. The alligator clamp is securely fastened to the end of the depth adjustment rod. The depth adjustment rod is positioned so that when the paper binder clip is lowered into the water, the entire fibrous nonwoven sheet sample is fully submerged in the water in the center of the beaker, the top of the fibrous nonwoven sheet sample is at the bottom of the vortex, and the bottom of the slide base / slide base holder is not in direct contact with the stirring rod. The depth adjustment rod and alligator clamp should be set so that the surface of the apertured film wall material sample is positioned perpendicular to the water flow.
[0183] In one motion, lower the secured slide and clamp into the water and start the timer. Drop the fibrous nonwoven sheet sample so that the sample is in the center of the beaker. Once all visible fibrous nonwoven sheet sample has come off the slide platform, raise the slide out of the water while continuing to monitor the solution for undissolved sample pieces. Dissolution has occurred when all sample pieces are no longer visible in the water. Record this as the dissolution time.
[0184] Three replicates of each sample are measured and the average dissolution time is reported within + / - 0.1 seconds. The average dissolution time is in seconds.
[0185] The average dissolution times are normalized for basis weight by dividing each by the sample basis weight as determined by the Basis Weight Method defined herein. Basis weight normalized average dissolution times are in seconds / gsm (s / (g / m2)) of the sample.
[0186] How to determine logP The log of the octanol / water partition coefficient (logP) is calculated for each PRM in the fragrance mixture being tested. The logP values of the individual PRMs are calculated using the Consensus logP Computational Model, version 14.02 (Linux), available from Advanced Chemistry Development Inc. (ACD / Lab), Toronto, Canada, which results in unitless logP values. The ACD / Labs Consensus logP Computational Model is part of the ACD / Labs model suite.
[0187] Average Shell Thickness Measurement The capsule shell, including the first shell component and, if present, the second shell component, is measured in nanometers for 20 delivery capsules containing beneficial agent using a focused ion beam scanning electron microscope (FIB-SEM, FEI Helios Nanolab 650) or equivalent instrument. Samples are prepared by diluting a small amount of liquid capsule dispersion (20 μl) with distilled water (1:10). The suspension is then deposited on an ethanol-cleaned aluminum stub and transferred to a carbon coating apparatus (Leica EM ACE600 or equivalent instrument). The samples are dried under vacuum in the coating apparatus (vacuum concentration: 10 -5 mbar). 25-50 nm of carbon is then flash deposited onto the sample to deposit a conductive carbon layer on its surface. The aluminum stub is then transferred to the FIB-SEM and a cross section of the capsule is prepared. Using a cross section cleaning pattern, cross sections are prepared by ion milling with an emission current of 2.5 nA at an accelerating voltage of 30 kV. Images are acquired at 5.0 kV and 100 pA using immersion mode (dwell time: approximately 10 microseconds) at a magnification of approximately 10,000x.
[0188] Images of the crushed shells are obtained in cross-section from 20 randomly selected benefit agent delivery capsules with no size bias to create a representative sample of the size distribution of capsules present. The shell thickness of each of the 20 capsules is measured at three different randomly selected locations using calibrated microscope software by drawing a measurement line perpendicular to the tangent plane of the outer surface of the capsule shell. Sixty independent thickness measurements are recorded and used to calculate the average thickness.
[0189] Mean and coefficient of variation of volume-weighted capsule diameter The capsule size distribution is determined by single particle optical detection (SPOS), also called optical particle counting (OPC), using an AccuSizer 780 AD instrument or equivalent and accompanying software CW788 version 1.82 (Particle Sizing Systems, Santa Barbara, Calif., USA) or equivalent. The instrument is configured with the following conditions and options: flow rate = 1 mL / sec; small diameter threshold = 0.50 μm; sensor model number = LE400-05SE or equivalent; autodilution = on; collection time: 60 seconds; number of channels = 512; reservoir fluid volume = 50 ml; maximum coincidence count = 9200. The measurement is started by cold-conditioning the sensor by flushing with water until the background count is less than 100. A sample of delivery capsules in suspension is introduced and the capsule density is adjusted, if necessary, via autodilution with deionized water to obtain a maximum capsule count of 9200 per mL. The suspension is analyzed for 60 seconds. The size range used was 1 μm to 493.3 μm.
[0190] Volume distribution:
[0191]
number
[0192]
number
[0193] Evaluation of volumetric core-to-shell ratio The value of the volumetric core-to-shell ratio is determined as follows and is dependent on the average shell thickness as measured by the Shell Thickness Test Method: The volumetric core-to-shell ratio for a capsule having a measured average shell thickness is calculated by the following equation:
[0194]
number
[0195] This ratio can be converted to a core to shell fraction value by calculating the core weight percentage using the following formula:
[0196]
number
[0197] Method for determining branching degree The branching degree of the precursor was determined as follows: The branching degree is measured using (29Si) nuclear magnetic resonance spectroscopy (NMR).
[0198] Sample preparation Each sample is diluted to a 25% solution using deuterated benzene (Benzene-D6 "100%" (D, 99.96%, available from Cambridge Isotope Laboratories Inc., Tewksbury, Massachusetts) or equivalent. 0.015 M chromium(III) acetylacetonate (99.99% purity, available from Sigma-Aldrich, St. Louis, Missouri, or equivalent) is added as a paramagnetic relaxation reagent. If glass NMR tubes (Wilmed-LabGlass, Vineland, New Jersey, or equivalent) are used for the analysis, a blank sample should also be prepared by filling the NMR tube with the same type of deuterated solvent used to dissolve the sample. The same glass tube should be used to analyze the blank and the sample.
[0199] Analysis of samples The degree of branching is determined using a Bruker 400 MHz nuclear magnetic resonance spectroscopy (NMR) instrument, or equivalent. A standard silicon (29Si) method (e.g., from Bruker) is used with default parameter settings, with a minimum of 1,000 scans and a relaxation time of 30 seconds.
[0200] Sample processing The samples are stored and processed using system software appropriate for NMR spectroscopy, such as MestReNova version 12.0.4-22023 (available from Mestrelab Research) or equivalent. Phase adjustment and background correction are applied. There is a large, broad signal extending from -70 to -136 ppm, which is a result of using glass NMR tubes as well as the glass present in the probe housing. This signal is suppressed by subtracting the spectrum of the blank sample from that of the synthetic sample, provided that the same tube and the same method parameters are used to analyze the blank and sample. To further account for slight differences in data collection, tubes, etc., the area outside the peak of interest should be integrated and normalized to a consistent value. For example, integrate from -117 to -115 ppm and set the integration value to 4 for all blanks and samples.
[0201] The resulting spectrum produces up to five main peak regions. The first peak (Q0) corresponds to unreacted TAOS. The second set of peaks (Q1) correspond to the end groups. The next set of peaks (Q2) correspond to the linear groups. The next set of broad peaks (Q3) are the semi-dendritic units. The final set of broad peaks (Q4) are the dendritic units. When PAOS and PBOS are analyzed, each group falls within a defined ppm range. Representative ranges are listed in the table below.
[0202] [Table 1]
[0203] Polymethoxysilanes have different chemical shifts for Q0 and Q1, overlapping signals for Q2, and Q3 and Q4 are unchanged, as shown in the table below.
[0204] [Table 2]
[0205] The ppm ranges shown in the table above may not apply to all monomers, however other monomers may give rise to different chemical shifts, but the proper assignment of Q0-Q4 should not be affected.
[0206] Using MestReNova, each peak group can be integrated and the branching degree can be calculated by the following formula:
[0207]
number
[0208] Molecular weight and polydispersity index determination method The molecular weight (polystyrene equivalent weight average molecular weight (Mw)) and polydispersity index (Mw / Mn) of the condensation layer precursors described herein are determined using size exclusion chromatography with refractive index detection, where Mn is the number average molecular weight.
[0209] Sample preparation The sample is weighed and then diluted to a target concentration of 10 mg / mL with the solvent used in the instrument system. For example, 50 mg of polyalkoxysilane is weighed into a 5 mL volumetric flask, dissolved, and diluted to a given volume with toluene. After the sample is dissolved in the solvent, it is passed through a 0.45 μm nylon filter and loaded into the instrument's autosampler.
[0210] Analysis of samples An HPLC system using an autosampler (e.g., Waters 2695 HPLC Separation Module, Milford, Massachusetts, or equivalent) connected to a refractive index detector (e.g., Wyatt 2414 Refractive Index Detector, Santa Barbara, Calif., or equivalent) is used for polymer analysis. Separation is performed on three columns, each 7.8 mm ID x 300 mm long, packed with 5 μm polystyrene-divinylbenzene media, with molecular weight cutoffs of 1, 10, and 60 kDA, respectively. Suitable columns are TSKGel G1000HHR, G2000HHR, and G3000HHR columns (available from TOSOH Bioscience, King of Prussia, Pa.) or equivalent. A 5 μm polystyrene-divinylbenzene guard column (e.g., TSKgel Guardcolumn HHR-L (TOSOH Biosciences), or equivalent), 6 mm ID×40 mm length, is used to protect the analytical column. Toluene (HPLC grade or equivalent) is pumped uniformly at 1.0 mL / min with both the column and detector maintained at 25° C. 100 μL of the prepared sample is injected for analysis. Sample data is stored and processed using software with GPC calculation capabilities (e.g., ASTRA Version 6.1.7.17 software available from Wyatt Technologies, Santa Barbara, Calif., or equivalent).
[0211] The system is calibrated using 10 or more narrowly dispersed polystyrene standards with known molecular weights ranging from about 0.250-70 kDa (e.g., Standard ReadyCal Set (e.g., Sigma-Aldrich, PN76552, or equivalent)) using a third-order fit to the Mp vs. retention time curve.
[0212] The system software is used to calculate and report the weight average molecular weight (Mw) and polydispersity index (Mw / Mn).
[0213] Method for calculating organic content in the first shell component As used herein, the definition of organic moieties within the inorganic shell of the capsule according to the present disclosure is that any moiety X that cannot be cleaved from a metal precursor having a metal M, where M belongs to the group of metals and metalloids and X belongs to the group of non-metals, by hydrolysis of the MX bond that connects said moiety to the inorganic precursor of the metal or metalloid M under certain reaction conditions is set as having a minimum degree of hydrolysis of 1% when exposed to distilled water having a neutral pH without stirring for 24 hours.
[0214] This method allows the calculation of the theoretical organic content, assuming complete conversion of all hydrolyzable groups. It thus becomes possible to evaluate the theoretical percentage of organic components for any mixture of silanes, the result of which represents only the organic content of this precursor mixture itself, and not the actual organic content in the first shell component. Therefore, if a specific percentage for the organic content of the first shell component is disclosed anywhere in this document, that percentage should be understood as containing any mixture of unhydrolyzed or prepolymerized precursors that gives a theoretical organic content smaller than the disclosed number according to the following calculation.
[0215] Examples of silanes include (but are not limited to) (see general formula at the end of this section): Each mole fraction Y i Consider a mixture of silanes having the formula: where i is the identification number of each silane. The mixture can be represented as: Si(XR) 4-n R n where XR is a group hydrolyzable under the conditions described above, and R i ni is non-hydrolyzable under the above conditions, and n i =0, 1, 2, or 3.
[0216] Such a mixture of silanes results in a shell having the general formula:
[0217]
number
[0218] The weight percentage of the organic portion, as defined above, can then be calculated as follows: 1) Find the mole fraction of each precursor (including nanoparticles). 2) Determine the general formula for each precursor (including nanoparticles). 3) Calculate the general formula for the mixture of precursors and nanoparticles based on the mole fractions. 4) Conversion to reacted silane (all hydrolyzable groups to oxygen groups). 5) Calculate the weight ratio of organic moieties to the total mass (assuming 1 mole of Si per framework).
[0219] Working Example:
[0220] [Table 3]
[0221] To calculate the general formula of a mixture, the indices of each atom in the individual formulas are multiplied by their respective mole fractions. Then, in the case of a mixture, when similar indices occur, the sum of the fractional indices is taken (typically for the ethoxy groups).
[0222] Note: The sum of all Si fractions will always sum to 1 in the mixture general formula due to the calculation method (total mole fractions of Si sum to 1). SiO 1*0.57+2*0.25 (OEt) 2*0.57+4*0.07+2*0.10 Me 2*0.10 SiO 1.07 (OEt) 1.62 Me 0.20
[0223] To convert the unreacted formula to the reacted formula, simply divide all the hydrolyzable group indices by 2 and then add them together (along with any existing oxygen groups, if applicable) to get the fully reacted silane. SiO 1.88 Me 0.20
[0224] In this case, the expected result is SiO since the sum of all the exponents must follow the formula: 1.9 Me 0.2 Is: A+B / 2=2, In the formula, A is the oxygen atom index and B is the sum of all non-hydrolyzable indexes. Small errors arise from taking round numbers in the calculation, which should be corrected. Then, readjust the oxygen atom index to satisfy this formula.
[0225] Therefore, the final formula is SiO 1.9 Me 0.2 and the weight ratio of the organic component is calculated as follows: Weight ratio=(0.20 * 15) / (28+1.9 * 16+0.20 * 15)=4.9%
[0226] General case: The above formula can be generalized by considering the valence of the metal or metalloid M, thus obtaining the following modified formula: M(XR) V-ni R i ni A similar method is used, but the valence V of each metal is taken into account.
[0227] Cleaning test and headspace analysis The method of treating the fabric involves the use of a commercial washing machine such as a Miele Honeycomb Care W1724 or similar machine using standard machine settings (cotton short cycle for 1 hour 14 minutes at 40° C., 1200 RPM, using water with 2.5 mmol / L hardness). The fabric composition in the washing machine consists of terry cotton and polyester test fabrics and a standard ballast load consisting of a blend of polycotton and cotton, totaling 3 kilograms.
[0228] Immediately after the wash cycle, the wet fabric tracers were subjected to perfume headspace analysis. For the examples using laundry detergent compositions, eight replicates of each type of tracer were analyzed by fast headspace GC / MS per wash test. For the examples using laundry additive compositions, four replicates were used. A 4x4 cm aliquot of fabric tracer was transferred into a 25 mL headspace bottle. The fabric samples were equilibrated at 65°C for 10 minutes. The headspace above the fabric was sampled by SPME (50 / 30 μm DVB / Carboxen / PDMS) technique for 5 minutes. The SPME fibers were then thermally desorbed on-line into the GC. The analytes were analyzed in full scan mode on the fast GC / MS. The total headspace response (expressed in nmol / l) on the test sections was determined by ion extraction of the specific masses of the perfume raw materials. EXAMPLES
[0229] The examples provided below are intended to be illustrative and not limiting in nature.
[0230] material The following materials were used in the following examples:
[0231] Fiber / non-woven substrate The purchased PVOH fibers were converted into nonwoven sheets by JIANGSU WISDOM NONWOVEN CO LTD. Address: No. 19, China Road, Wu Jin, Changzhou, Jiangsu, RenMinDong. The weight composition of the fibers was as follows: · 95% by weight PVOH homopolymer 100-120 kDa; degree of hydrolysis 86-89%); · 5 wt% PEG600 gel breaker.
[0232] Flavor capsules and related slurries Two types of fragrances are provided: fragrance 1 and fragrance 2. The fragrances are encapsulated in two types of fragrance capsules, the synthetic routes of which are described below.
[0233] A. Silica Shell-Based Fragrance Capsules (Capsules According to the Present Disclosure) The oil phase was prepared by mixing 44 g of the non-hydrolyzed precursor (see below) with 88.75 g of Perfume 1 or Perfume 2 and homogenizing.
[0234] The aqueous phase was prepared by adding 7.6 g of Aerosil 300 (available from Evonik) to 374 g of 0.1 M HCl (available from Sigma Aldrich) in a glass vessel and then dispersed at 20000 rpm for 10 minutes using an IKA S25N-25F Ultraturrax rotor stator. If heat was generated during dispersion, the solution was cooled to room temperature before use.
[0235] After each phase was prepared separately, the aqueous phase was added to a vessel with a diameter of 10 cm. The oil phase was then slowly added to the vessel over a period of 30 seconds using a S25N-25F ultraturrax (IKA) mixing tool at 7000 rpm, after which emulsification was continued in the same vessel with the same mixing tool at 7000 rpm for 2 minutes.
[0236] Once the emulsification process was complete, the resulting emulsion was cured in a 500 ml jacketed glass reactor with mixing at 80 rpm using the following temperature profile: 4 hours at 30° C., 20 hours at 90° C., and another 2 hours at 30° C. This resulted in capsules of the present invention comprising a first shell component surrounding Perfume 1, the first shell component comprising a nanoparticle layer surrounding a condensation precursor.
[0237] To deposit the second shell component, 125 g of the above capsule slurry was added to a glass vessel equipped with a suspension stirrer stirring at 360 rpm. Next, 16 ml of a 10 wt. % solution of sodium metasilicate (available from Sigma Aldrich) in deionized water solution was added at a rate of 80 microliters / min using a syringe pump (Harvard apparatus) to raise the pH of the solution from 1.2 to 7, and once the pH of the mixture began to rise above 7, a second pump was turned on to simultaneously inject 1.6 M HCl (aqueous) so that the pH remained between 6.5 and 7.5 for the remainder of the addition of the sodium metasilicate solution.
[0238] After the injection of the second shell component solution was completed, the capsules were centrifuged at 2500 rpm for 10 minutes and redispersed in deionized water. The resulting capsules contained a silica-based first shell component and a second shell component according to the present disclosure.
[0239] 1. Synthesis of non-hydrolyzable precursors 1000 g of tetraethoxysilane (TEOS, available from Sigma Aldrich) was added to a clean, dry round-bottom flask equipped with a stir bar and distillation apparatus under a nitrogen atmosphere. 431 g of acetic anhydride (available from Sigma Aldrich) and 5.8 g of tetrakis(trimethylsiloxy)titanium (available from Gelest) were added and the contents of the flask were vigorously stirred at 135° C. for 16 hours. Next, an additional 107 g of acetic anhydride was added to the mixture, which was then heated at 135° C. for an additional 32 hours. During this time, ethyl acetate formed by the reaction of the ethoxysilane groups with acetic anhydride was distilled off. The reaction flask was cooled to room temperature and placed on a rotary evaporator (Buchi Rotovapor R110) which was used with a water bath and a vacuum pump (Welch 1402 DuoSeal) to remove any remaining solvent and volatile compounds. The polyethoxysilane (PEOS) produced was a yellow viscous liquid with the following specifications seen in Table A. The ratio of TEOS to acetic anhydride can be varied to control the parameters shown in Table A.
[0240] [Table 4]
[0241] B. Polyacrylate shell type fragrance capsule (comparison capsule) A population of perfume capsules comprising a polyacrylate shell and encapsulating perfume 1 were prepared according to the capsules manufactured according to the methods disclosed in U.S. Publication No. 2011 / 0268802.
[0242] C. Freeze-drying the liquid slurry of capsules The above synthesis descriptions for silica shell-based capsules and polyacrylate shell-based capsules resulted in liquid containing capsules. In order to incorporate them into a dry laundry formulation, the capsules were first freeze-dried. The freeze-drying process was as follows: 1) 100 g of the slurry was introduced into a 600 ml glass vessel suitable for the particular freeze-drying apparatus. The capsule slurry was then frozen at -80°C for 1 hour. 2) Once the slurry was frozen, the glass vessel was attached to a freeze dryer (Telstar LyoQuest-85 plus or equivalent) and the pressure was then reduced to 2-3 mBar and the slurry was dried for a minimum of 24 hours depending on whether all the water had been removed. 3) After drying the capsules, freeze-dried capsule powder was obtained.The freeze-dried capsule powder was then analyzed by TGA (rapid heating to 500°C at 20°C / min) to evaluate whether there was residual water and to calculate the perfume activity of the dried capsules (perfume activity is defined as the weight % of perfume in the powder sample).If water still existed, the capsules were further dried without the freezing step.
[0243] Laundry additive composition The laundry additive composition containing the capsules is prepared according to the following procedure. 1) 93.2 g of citric acid granules was added to a mixing vessel (Kenwood) equipped with a K-type mixing paddle. 2) A powder mix was then prepared consisting of 12 g of lyophilized capsules, 30 g of powdered citric acid (available from Sigma-Aldrich), and 16 g of monosodium citrate (available from Sigma Aldrich), resulting in a total mass of 58 g for the powder mix. 3) 1.8 g of a 35% by weight starch solution (made by dissolving starch available from Sigma Aldrich in water) was added to the atomizer. 4) Once all three mixtures (i.e., citric acid granules, powdered ingredients and starch solution in the mixing bowl) were prepared, 10% of the starch solution was sprayed onto the citric acid granules and 10% of the powder mixture from step 2 was added while mixing at the lowest setting in the mixing bowl. Once homogenous, an additional 10% of the starch solution was added, followed by an additional 10% of the powder mixture, and this iteration was repeated until all of the starch and powder mixture had been used.
[0244] Laundry detergent compositions A laundry detergent composition containing the capsules is prepared according to the following procedure. A powder laundry detergent composition containing 90 g of perfume capsules was prepared by mixing powder detergent (Standard Detergent Type A from WFK) and freeze-dried capsules together with a spoon until a uniform distribution of the capsules in the powder mix was obtained, targeting 0.5% perfume by weight in the final formula.
[0245] Example 1. Effect of PVOH on silica-based shell capsules in laundry additives To test the effect that polyvinyl alcohol (PVOH) has on silica-based shell perfume capsules in a laundry additive composition, the following experiment was conducted.
[0246] Two test sections (see Table 1A, section 1 is the comparative test section) were prepared by adding the components of each composition below to 2 L of water.
[0247] [Table 5]
[0248] 79 grams of detergent powder type A (WFK) was added to the drum before the start of the wash test. The two pre-dissolved fractions were then added to each washing machine by adding them to the fabric softener container during the final rinse of the wash program. The wash test protocol is described in the Test Method section above.
[0249] Table 1B summarizes the total perfume headspace response (in nmol / L) to a wet terry cotton tracer for silica shell capsules according to the present disclosure, as well as the single variable headspace loss / gain effect of the addition of a polyvinyl alcohol nonwoven pouch.
[0250] [Table 6] *Concentrations not linked with the same letter are significantly different (Student's t test).
[0251] As shown by the results in Table 1B, the total perfume headspace of the silica-based shell capsule in the rinse-add laundry additive composition is increased by 40% when combined with a polyvinyl alcohol nonwoven pouch.
[0252] Example 2. Effect of PVOH on different perfume capsules in detergent To test the effect that polyvinyl alcohol (PVOH) has on different perfume capsules in a laundry detergent composition, the following experiment was performed.
[0253] Four test sections were prepared as shown in Table 2A. Sections 1, 3 and 4 were comparative test sections.
[0254] [Table 7]
[0255] Each of the above formulations was then added to the drum of each washing machine and run according to the wash test described in the Test Methods section above.
[0256] Table 2B summarizes the total perfume headspace response (in nmol / L) to the wet terry cotton tracer, as well as the single variable headspace loss / gain effect of the addition of the polyvinyl alcohol nonwoven pouch.
[0257] [Table 8] * Concentrations not linked with the same letter are significantly different (Student's t test).
[0258] As shown by the results in Table 2B, the data indicates a positive perfume headspace impact of the polyvinyl alcohol nonwoven pouch on the terry cotton tracer headspace (+25% total headspace) when combined with silica shell capsules in the context of a laundry detergent.
[0259] The results in Table 2B also show the adverse effect of polyvinyl alcohol nonwoven pouches (approximately 8% total headspace) when combined with polyacrylate shell capsules in the context of laundry detergent. In addition, it is worth noting that while polyacrylate-based shell capsules provided relatively large headspace values, such shell materials may be of petrochemical origin and therefore less preferred for sustainability reasons.
[0260] Example 3. Effect of PVP on different perfume capsules in detergent The following experiment was conducted to test the effect that polyvinylpyrrolidone ("PVP") has on different perfume capsules: To create a single variable experiment, a pre-dissolved form of the fabric treatment composition was created.
[0261] Four test sections were formulated, as shown in Table 3A below. In each, a surfactant paste mixture was provided and dissolved in water to simulate a cleaning solution. The surfactant paste mixture consisted of sodium lauryl sulfate, sodium linear alkylbenzene sulfonate, and polyethylene oxide oligomer (average n=10 for monomer repeat unit).
[0262] To simulate a wash liquor, 16.5g of demineralized water was added to a plastic container. 3.15g of surfactant paste was added to the water, and the mixture was placed on a laboratory shaker at 300 rpm for 1 hour or until the surfactant paste was completely dissolved. Next, perfume capsules and PVP polymer (PVP-k60 from Jarchem) if any were added to the mixture while mixing with an overhead mixer at 500 rpm until the capsules were dispersed (see Table 3A). This mixture was now ready to be used in the washing machine test.
[0263] [Table 9]
[0264] Each of the above formulations was then added to the drum of each washing machine and run according to the wash test described in the Test Methods section above.
[0265] Table 3B summarizes the total perfume headspace response (in nmol / L) to the wet terry cotton tracer, as well as the single variable headspace loss / gain effect of the addition of the polyvinyl alcohol nonwoven pouch.
[0266] [Table 10] * Concentrations not linked with the same letter are significantly different (Student's t test).
[0267] The results in Table 3B show an increase in total wet headspace (+18%) when PVP is included in the cleaning slurry with silica shell capsules, while showing a negative impact (-11%) when PVP is combined with polyacrylate shell capsules. Furthermore, as explained above, polyacrylate-based capsules can be of petrochemical origin and therefore are less preferred.
[0268] Dimensions and values disclosed herein should not be understood as being strictly limited to the exact numerical values recited. Instead, unless otherwise specified, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."
[0269] All documents cited herein, including any cross-referenced or related patents or patent applications, and any patent applications or patents to which this application claims priority or benefit, are incorporated herein by reference in their entirety, unless expressly stated to the contrary. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest, or disclose any such invention, either alone or in combination with any other reference or references. Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition given to that term in this document shall govern.
[0270] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.
Claims
1. A water-soluble unit dose article comprising a water-soluble fibrous nonwoven substrate and a particulate treatment composition, The substrate comprises a plurality of fibers; the fibers comprise a water-soluble polymer; the particulate treatment composition comprises a capsule; The capsule includes a core and a shell surrounding the core, said core comprising a benefit agent; A water soluble unit dose article wherein the shell comprises an inorganic material.
2. 10. The water soluble unit dose article of claim 1, wherein the water soluble fibrous nonwoven substrate has a basis weight of 20 gsm to 60 gsm.
3. 3. The water-soluble unit dose article of claim 1 or 2, wherein the water-soluble fibrous nonwoven substrate is in the form of a sheet molded to form at least one sealed internal compartment, and the treatment composition is contained in the sealed internal compartment.
4. The water soluble unit dose article of any one of claims 1 to 3, wherein the capsules are mixed with the plurality of fibers of the water soluble fibrous nonwoven substrate.
5. The water soluble unit dose article of any one of claims 1 to 4, wherein the water soluble polymer comprises polyvinyl alcohol, polyvinylpyrrolidone, starch, carboxymethyl cellulose, polyethylene oxide, derivatives thereof, or combinations thereof.
6. The fibers further comprise a gel breaker; The water soluble unit dose article of any one of claims 1 to 5, wherein the gel breaking agent is selected from a polyol, a sugar alcohol, an amine, an amide, a carbohydrate, a multivalent cation, or a mixture thereof.
7. The water soluble unit dose article of any one of claims 1 to 6, wherein the benefit agent comprises a fragrance.
8. The water soluble unit dose article of any one of claims 1 to 7, wherein the shell of the capsule comprises from about 90% to about 100% of the inorganic material by weight of the shell.
9. The water soluble unit dose article of any one of claims 1 to 8, wherein the inorganic material in the shell comprises a material selected from a metal oxide, a semi-metal oxide, a metal, a mineral, or a mixture thereof.
10. The shell is (a) a first shell component comprising a condensation layer and a nanoparticle layer, the condensation layer comprising a condensation product of precursors and the nanoparticle layer comprising inorganic nanoparticles, the condensation layer being disposed between the core and the nanoparticle layer; (b) a second shell component surrounding the first shell component, the second shell component surrounding the nanoparticle layer.
11. The capsule comprises: (a) an average volume-weighted capsule diameter of about 1 μm to 250 μm; (b) an average shell thickness of about 170 nm to about 1000 nm; (c) a volume core to shell ratio of about 50:50 to about 99:1; (d) the first shell component comprises an organic content of about 5% by weight or less, based on the weight of the first shell component; or (e) mixtures thereof; The water-soluble unit dose article of any one of claims 1 to 10, characterized by one or more of the following:
12. The precursor comprises at least one compound selected from the group consisting of formula (I), formula (II), or a mixture thereof; Formula (I) is a compound represented by the formula (M v O z Y n ) w and Formula (II) is represented by the formula (M v O z Y n R 1 p ) w and For formula (I), formula (II), or a mixture thereof: Each M is independently selected from the group consisting of silicon, titanium, and aluminum; v is the valency of M and is about 3 or about 4; z is from about 0.5 to about 1.6; Each Y is -OH, -OR 2 ,halogen, 【Chemistry 1】 are independently selected from R 2 is C 1 ~C 20 Alkyl, C 1 ~C 20 Alkylene, C 6 ~C 22 aryl, or a 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S; R 3 is H, C 1 ~C 20 Alkyl, C 1 ~C 20 Alkylene, C 6 ~C 22 aryl, or a 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S; w is from about 2 to about 2000; For formula (I), n is from 0.7 to (v-1); and For formula (II), n is 0 to (v-1); Each R 1 is C 1 ~C 30 Alkyl; C 1 ~C 30 Alkylene; halogen, -OCF 3 , -NO 2 , -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, -CO 2 C substituted with a member selected from the group consisting of H, —C(O)-alkyl, —C(O)O-aryl, and —C(O)O-heteroaryl. 1 ~C 30 Alkyl; and halogen, -OCF 3 , -NO 2 , -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, -C(O)OH, -C(O)O-alkyl, -C(O)O-aryl, and -C(O)O-heteroaryl. 1 ~C 30 alkylene; p is a number from 0 to pmax, pmax=60 / [9 * Mw(R 1 ) + 8], Mw(R 1 ) is R 1 The water soluble unit dose article of any one of claims 1 to 11, wherein the molecular weight of the group is 1.
13. The water soluble unit dose article of any one of claims 1 to 12, wherein for said compounds of formula (I), formula (II), or both, M is silicon.
14. One or both of the compounds of formula (I) and formula (II) are (a) a polystyrene equivalent weight average molecular weight (Mw) of about 700 Da to about 30,000 Da; (b) a degree of branching of about 0.2 to about 0.6; (c) a molecular weight polydispersity index of from about 1 to about 20; or (d) mixtures thereof; The water-soluble unit dose article of any one of claims 1 to 13, characterized by one or more of the following:
15. 15. The water soluble unit dose article of any one of claims 1 to 14, wherein for formula (I), formula (II), or both, Y is OR, and R is selected from a methyl group, an ethyl group, a propyl group, or a butyl group.
Citation Information
Patent Citations
Water-soluble unit dose article
EP3919601A1
Production method of microcapsule
JP2015128762A
capsules
WO2020214876A1